Laminated film, method for producing laminated film, conductive film, current collector, and battery

By controlling the thickness ratio and surface wetting index of the intermediate layer to the outer layer, optimizing the resin composition and coextrusion process, the thickness fluctuation and peelability of the conductive film intermediate layer are solved, and a laminated film with high conductivity and good appearance is achieved, which is suitable for current collectors and batteries.

CN120303117APending Publication Date: 2025-07-11MITSUBISHI CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380082868.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-30
Filing Date
2023-11-17
Publication Date
2025-07-11

AI Technical Summary

Technical Problem

In the prior art, it is difficult to produce a conductive film with small thickness fluctuations, good appearance and high conductivity. Especially when the intermediate layer is less than 100 μm, there are problems with the peelability and coating properties between the intermediate layer and the outer layer.

Method used

By controlling the thickness ratio (Y/X) of the intermediate layer to the outer layer within a range of 1 to 5, the thickness of the intermediate layer fluctuates less than ±10 μm, and the surface wetting index of the intermediate layer is 30dyne/cm or more, a multi-layer structure and a specific resin composition are used to optimize the coextrusion process to stabilize the interface.

Benefits of technology

A laminated film with excellent peelability of the intermediate layer and the outer layer with small thickness fluctuations, good appearance and high conductivity is realized, which improves the surface quality and productivity of the conductive film, and is suitable for current collectors and batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005428675910000351
    Figure BDA0005428675910000351
  • Figure BDA0005428675910000401
    Figure BDA0005428675910000401
  • Figure BDA0005428675910000451
    Figure BDA0005428675910000451
Patent Text Reader

Abstract

A laminated film having an intermediate layer [I] comprising a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] comprising a resin composition (B) containing a thermoplastic resin (b1), the thickness (X) of the intermediate layer [I] being 1 [mu] m-100 [mu] m, the ratio (Y / X) of the thickness (Y) of the two outer layers [II] to the thickness (X) of the intermediate layer [I] being 1-5, the fluctuation in the thickness of the intermediate layer [I] being less than + / -10 [mu] m, and the thickness of the intermediate layer [I] being 1-10 [mu] m. And the peel strength of the middle layer [I] and the two outer layers [II] is less than 0.1 N / cm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated film, a method for manufacturing the laminated film, a conductive film, a current collector, and a battery. Background Art

[0002] In the electronic field, the main properties required of polymer materials vary depending on the product and application, and include moldability, heat resistance, durability, high strength, chemical resistance, corrosion resistance, etc. As resins that meet these requirements, thermoplastic resins such as polypropylene, polycarbonate, and polyimide, and thermosetting resins such as epoxy resin and phenolic resin can be cited.

[0003] In order to impart conductivity to a polymer material, a method of adding a conductive material to the polymer material is known. However, in order to obtain a highly conductive film with a volume resistivity of 10 4 Ω·cm or less, a large amount of conductive material has to be added to the polymer material, and there are cases where the extrusion moldability deteriorates. Therefore, many studies have been reported.

[0004] For example, Patent Document 1 discloses a method for manufacturing a highly conductive film, which is characterized in that a highly conductive thermoplastic resin composition layer containing 30 parts by weight or more of a carbon-based filler is used as an intermediate layer, and a peelable thermoplastic resin layer is co-extruded on both sides thereof as an outer layer. The force required for peeling the outer layer in the 180° direction with respect to the intermediate layer is 5 to 500 g / 15 mm width. After cooling, the thermoplastic resin layers on both sides are peeled off.

[0005] In addition, Patent Document 2 discloses a method for manufacturing a highly conductive film, which is characterized in that a multilayer film is produced by a co-extrusion method, the multilayer film having an intermediate layer composed of a conductive resin composition in which a conductive filler is blended in a thermoplastic resin (A), and thermoplastic resins (B) having good peelability from the above-mentioned thermoplastic resin (A) disposed on both outer layers thereof. After cooling the multilayer film, the two outer layers are peeled off, and the ratio D / L of the draw ratio D to the die lip gap L during co-extrusion is 11 or less.

[0006] In addition, Patent Document 3 discloses a laminated film having: an intermediate layer composed of a resin composition (I) containing a conductive filler (A) and a thermoplastic resin (B), and two outer layers composed of a resin composition (II) containing a thermoplastic resin (C). The ratio [MFR(I) / MFR(II)] of the melt flow rate (MFR(I)) of the resin composition (I) to the melt flow rate (MFR(II)) of the resin composition (II) is 0.1 to 3.5. The average value of the first normal stress difference at a temperature of 240°C and a shear rate of 10 to 100 sec -1 of the resin composition (I) is -0.015 MPa or more, and the thickness of the intermediate layer is 50 μm or less.

[0007] Prior art documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Laid-Open No. 61-82611

[0010] Patent Document 2: Japanese Patent Laid-Open No. 2014-030899

[0011] Patent Document 3: Japanese Patent Laid-Open No. 2020-157651 Summary of the invention

[0012] As a method for manufacturing a laminated film, for example, the following method can be cited: using an extrusion molding machine, the resin composition for the intermediate layer and the resin composition for the outer layer are respectively put into the hopper of the extruder, melted and plasticized at a specified temperature, co-extruded from the lip die gap which is the T-die nozzle under specified film-forming conditions, introduced to a casting roll at a specified temperature, and then cooled and solidified to obtain a laminated film.

[0013] In recent years, with the miniaturization and thinning of electronic components, in the conductive films used as part of such electronic components, the requirements for weight reduction and film thinning have been continuously increasing. Therefore, if the thickness of the desired intermediate layer is set to 100 μm or less, since it is a thin film, when manufacturing a laminated film, the resin composition for the intermediate layer extruded from the nozzle of the T-die is easily affected by the components around the nozzle it contacts. As a result, the thickness fluctuation of the intermediate layer becomes larger, and there are problems such as appearance defects such as uneven flow and hole opening in the intermediate layer, and problems such as unstable peeling of the outer layer when peeling the outer layer from the laminated film, resulting in stick-slip (jamming).

[0014] In the manufacturing methods of the conductive films disclosed in Patent Documents 1 and 2, research has been conducted to obtain a film with higher conductivity. However, in Patent Documents 1 and 2, there has been no special research on obtaining a laminated film with small thickness fluctuation, good appearance, and excellent peelability between the intermediate layer and the two outer layers even when the desired intermediate layer is as thin as 100 μm or less, and there is room for further research.

[0015] Generally, the peel strength when peeling the outer layer from the laminated film is determined by considering the following matters, that is, suppressing the defect of the outer layer peeling from the intermediate layer during winding of the laminated film, and preventing peeling defects such as a part of the outer layer adhering to the intermediate layer when peeling the outer layer from the laminated film. For example, Patent Document 3 provides the following laminated film, where the peel strength between the intermediate layer and the two outer layers is 0.1 N / cm to 1.4 N / cm.

[0016] In recent years, from the viewpoints of improving the surface quality of the conductive film, improving the conductive film, and increasing the productivity of the current collector using the conductive film and the battery using the conductive film, it has been required to smoothly and quickly peel off the outer layer from the intermediate layer, that is, to further reduce the peel strength between the intermediate layer and the two outer layers.

[0017] In addition, in recent years, attempts have been made to use a conductive film as a current collector for a negative electrode, and a negative electrode layer is formed by coating a negative electrode coating material (for example, an aqueous negative electrode coating material obtained by mixing a negative electrode active material, a binder, and an aqueous solvent) on the surface of the current collector for a negative electrode to manufacture a battery. When forming the negative electrode layer, it is required to uniformly coat the negative electrode coating material (especially the aqueous negative electrode coating material) on the surface of the current collector for a negative electrode. However, there are problems such as the negative electrode coating material being repelled on the surface of the current collector for a negative electrode, resulting in unevenness, and thus the negative electrode coating material cannot be uniformly coated.

[0018] In the manufacturing methods of highly conductive films disclosed in Patent Documents 1 and 2, and in the laminated films having an intermediate layer that can be a conductive film disclosed in Patent Document 3, research has been conducted to obtain a film with higher conductivity. However, in Patent Documents 1 to 3, when the conductive film is used as a current collector for a negative electrode, there has been no particular research on modifying the surface characteristics of the current collector for a negative electrode to uniformly coat the negative electrode coating material, and there is room for further research.

[0019] Therefore, the object of the first aspect of the present invention is to provide a laminated film having an intermediate layer that is thin with a thickness of 100 μm or less, has small thickness fluctuations, good appearance, and high conductivity, and excellent peelability between the intermediate layer and the two outer layers.

[0020] In addition, the object of the second aspect of the present invention is to provide a laminated film having an intermediate layer with small thickness fluctuations, excellent coatability of an aqueous liquid, good appearance, and high conductivity, and excellent peelability between the intermediate layer and the two outer layers. Further, the object of the second aspect of the present invention is to provide a conductive film with small thickness fluctuations, excellent coatability of an aqueous liquid, good appearance, and high conductivity.

[0021] In addition, the object of the third aspect of the present invention is to provide a laminated film having an intermediate layer with excellent coatability of an aqueous liquid, excellent mechanical properties such as elongation at break in tension, small thickness fluctuations, good appearance, and high conductivity, and excellent peelability between the intermediate layer and the two outer layers. Further, the object of the third aspect of the present invention is to provide a conductive film with excellent coatability of an aqueous liquid, excellent mechanical properties such as elongation at break in tension, small thickness fluctuations, good appearance, and high conductivity.

[0022] The present inventors have found that: regarding the first mode of the present invention, even when the intermediate layer is a thin film with a thickness of 1 μm to 100 μm, by making the thickness ratio (Y / X) of the thicknesses of the two outer layers (Y) to the thickness of the intermediate layer (X) within a specific range, making the thickness fluctuation of the intermediate layer less than a specific range, and further making the peeling strength between the intermediate layer and the two outer layers less than a specific range, the above problems can be solved.

[0023] The present inventors have found that: regarding the second mode of the present invention, by making the thickness fluctuation of the intermediate layer less than a specific range (less than ±10 μm) and making the surface wetting index of at least one side of the intermediate layer a specific value or more (30 dyne / cm or more), the above problems can be solved.

[0024] The present inventors have found that: regarding the third mode of the present invention, by making the intermediate layer [I] a layer formed of multiple layers and making the surface wetting index of at least one surface layer (i - 1) of the intermediate layer a specific value or more (30 dyne / cm or more), the above problems can be solved.

[0025] That is, the present invention provides the following modes.

[0026] <1> A laminated film having an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1),

[0027] The thickness (X) of the intermediate layer [I] is 1 μm to 100 μm,

[0028] The ratio (Y / X) of the thickness (Y) of the two outer layers [II] to the thickness (X) of the intermediate layer [I] is 1 to 5,

[0029] The thickness fluctuation of the intermediate layer [I] is less than ±10 μm,

[0030] The peeling strength between the intermediate layer [I] and the two outer layers [II] is less than 0.1 N / cm.

[0031] <2> The laminated film according to <1> above, wherein the thermoplastic resin (a1) is a polyolefin resin.

[0032] <3> The laminated film according to <1> or <2> above, wherein the conductive filler (a2) is at least one selected from carbon nanotubes and carbon black.

[0033] <4> The laminated film according to any one of <1> to <3> above, wherein the thermoplastic resin (b1) is one or more selected from polyester resins, polycarbonate resins, and polystyrene resins.

[0034] <5>The laminated film according to any one of <1> to <4> above, wherein the content of the conductive filler (a2) in the resin composition (A) is 0.1% by mass to 50% by mass.

[0035] <6>A method for manufacturing a laminated film, which is a method for manufacturing the laminated film according to any one of <1> to <5> above,

[0036] A resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2) and a resin composition (B) containing a thermoplastic resin (b1) are co-extruded to form a film.

[0037] The ratio (x1 / X) of the thickness (x1) of the intermediate layer [I] at the die lip during co-extrusion to the thickness (X) of the intermediate layer [I] of the laminated film after film formation is 1 to 40.

[0038] <7>The method for manufacturing a laminated film according to <6> above, wherein the thickness (x1) of the intermediate layer [I] at the die lip during co-extrusion is 40 μm to 500 μm.

[0039] <8>The method for manufacturing a laminated film according to <6> or <7> above, wherein the thickness (X) of the intermediate layer [I] of the laminated film after film formation is 1 μm to 100 μm.

[0040] <9>A laminated film having: an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1),

[0041] The thickness fluctuation of the intermediate layer [I] is less than ±10 μm,

[0042] The surface wetting index of at least one side of the intermediate layer [I] is 30 dyne / cm or more.

[0043] <10>The laminated film according to <9> above, wherein the resin composition (A) contains a carboxylic acid-modified polyolefin resin (a3).

[0044] <11>The laminated film according to <10> above, wherein the content of the carboxylic acid-modified polyolefin resin (a3) in the resin composition (A) is 5% by mass to 50% by mass.

[0045] <12>A laminated film having: an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1),

[0046] The intermediate layer [I] is a layer formed by multiple layers.

[0047] The surface wetting index of at least one surface layer (i - 1) of the intermediate layer [I] is 30 dyne / cm or more.

[0048] <13> The laminated film according to <12> above, wherein at least one surface layer (i - 1) of the intermediate layer [I] is a layer formed of a resin composition (A1) containing a thermoplastic resin (a1), a conductive filler (a2), and a carboxylic acid-modified polyolefin resin (a3).

[0049] <14> The laminated film according to <13> above, wherein the content of the carboxylic acid-modified polyolefin resin (a3) in the resin composition (A1) is 5% by mass to 50% by mass.

[0050] <15> The laminated film according to any one of <12> to <14> above, wherein the intermediate layer [I] is a two-layer structure of surface layer (i - 1) / middle layer (i - 2), or a three-layer structure of surface layer (i - 1) / middle layer (i - 2) / surface layer (i - 1).

[0051] <16> The laminated film according to <15> above, wherein the middle layer (i - 2) of the intermediate layer [I] is a layer formed of a resin composition (A2) containing a thermoplastic resin (a1) and a conductive filler (a2) and substantially not containing a carboxylic acid-modified polyolefin resin (a3).

[0052] <17> The laminated film according to any one of <12> to <16> above, wherein the thickness fluctuation of the intermediate layer [I] is less than ±10 μm.

[0053] <18> The laminated film according to any one of <9> to <17> above, wherein the thickness (X) of the intermediate layer [I] is 1 μm to 100 μm, and the ratio (Y / X) of the thickness (Y) of each layer of the two outer layers [II] to the thickness (X) of the intermediate layer [I] is 1 to 5.

[0054] <19> The laminated film according to any one of <9> to <18> above, wherein the peel strength between the intermediate layer [I] and the two outer layers [II] is less than 0.1 N / cm.

[0055] <20> The laminated film according to any one of <9> to <19> above, wherein the thermoplastic resin (a1) is a polyolefin resin.

[0056] <21> The laminated film according to any one of <9> to <20> above, wherein the conductive filler (a2) is a carbon nanotube.

[0057] <22> The laminated film according to any one of <9> to <21> above, wherein the thermoplastic resin (b1) is a polyester resin.

[0058] <23> The laminated film according to any one of <9> to <22> above, wherein the content of the conductive filler (a2) in the resin composition (A) is 0.1% by mass to 50% by mass.

[0059] <24> The laminated film according to any one of <1> to <5>, <9> to <23> above, wherein the thickness of the laminated film is 20 μm to 400 μm.

[0060] <25> The laminated film according to any one of <1> to <5>, <9> to <24> above, wherein the thickness of each layer of the two outer layers [II] is 5 μm to 150 μm.

[0061] <26> A conductive film obtained by peeling off the two outer layers [II] of the laminated film according to any one of <1> to <5>, <9> to <25> above.

[0062] <27> A current collector using the conductive film described in <26> above.

[0063] <28> A battery using the conductive film described in <26> above.

[0064] <29> A laminated film having: an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1).

[0065] The resin composition (A) contains a carboxylic acid-modified polyolefin resin (a3).

[0066] According to the first aspect of the present invention, it is possible to provide a laminated film having an intermediate layer that has a small thickness fluctuation even when the intermediate layer is as thin as 100 μm or less, has a good appearance, has high conductivity, and has excellent peelability between the intermediate layer and the two outer layers. In addition, according to the present invention, the intermediate layer obtained by peeling off the two outer layers from the laminated film can be particularly advantageously used for the use of a conductive film.

[0067] According to the second aspect of the present invention, it is possible to provide a laminated film having an intermediate layer with a small thickness fluctuation, excellent coatability of an aqueous liquid, a good appearance, and high conductivity, and also having excellent peelability between the intermediate layer and the two outer layers. In addition, according to the second aspect of the present invention, it is possible to provide a conductive film having a small thickness fluctuation, excellent coatability of an aqueous liquid, a good appearance, and high conductivity.

[0068] According to the third aspect of the present invention, a laminated film can be provided, which has an intermediate layer with excellent coatability of aqueous liquid, excellent mechanical properties such as tensile elongation at break, small thickness fluctuation, good appearance, and high conductivity, and also has excellent peelability between the intermediate layer and the two outer layers. In addition, according to the third aspect of the present invention, a conductive film with excellent coatability of aqueous liquid, excellent mechanical properties such as tensile elongation at break, small thickness fluctuation, good appearance, and high conductivity can be provided. Detailed Embodiments

[0069] Hereinafter, the present invention will be described in detail. However, the content of the present invention is not limited to the embodiments described below.

[0070] <Term Explanation>

[0071] In the present invention, when expressed as "X to Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meanings of "X or more and Y or less", "preferably greater than X", and "preferably less than Y".

[0072] [Laminated Film]

[0073] The laminated film in the first aspect of the present invention has: an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1). The thickness (X) of the intermediate layer [I] is 1 μm to 100 μm, the ratio (Y / X) of the thickness (Y) of the two outer layers [II] to the thickness (X) of the intermediate layer [I] is 1 to 5, the thickness fluctuation of the intermediate layer [I] is less than ±10 μm, and the peel strength between the intermediate layer [I] and the two outer layers [II] is less than 0.1 N / cm.

[0074] It should be noted that the thickness of the intermediate layer [I] and the thickness of the two outer layers [II] can be set by appropriately adjusting the extrusion amount or extrusion speed of the resin composition, the temperature or pulling speed of the casting roll, the lip die gap of the T-die head, the resin temperature during extrusion, etc.

[0075] In addition, the peel strength between the intermediate layer [I] and the two outer layers [II] can be set by making the ratio (Y / X) of the thickness (Y) of the two outer layers [II] to the thickness (X) of the intermediate layer [I] be 1 to 5, and appropriately adjusting the type of the conductive filler (a2), the type of the resin constituting the two outer layers [II], the melt viscosity of the resin constituting the intermediate layer [I], and the melt viscosity of the resin constituting the two outer layers [II].

[0076] According to the first aspect of the present invention, the following effects are achieved: It is possible to provide a laminated film having an intermediate layer that is as thin as 100 μm or less, has small thickness fluctuations, good appearance, high conductivity, and excellent peelability between the intermediate layer and the two outer layers. The reason is not clear yet, but it is considered as follows.

[0077] It is considered that when manufacturing the laminated film, the resin composition for the intermediate layer extruded from the discharge port of the T-die is affected by the components around the discharge port it contacts, making the interface between the formed intermediate layer and the two outer layers unstable. Therefore, the thickness fluctuations of the intermediate layer become larger, the appearance of the intermediate layer deteriorates, and when peeling the outer layer from the laminated film, the peeling of the outer layer is unstable and stick-slip (jamming) occurs.

[0078] The inventors conducted in-depth research and found that even if the desired intermediate layer is a thin film of 100 μm or less, by making the thickness ratio (Y / X) of the thickness (Y) of the two outer layers to the thickness (X) of the intermediate layer within a specific range (1 to 5), making the thickness fluctuations of the intermediate layer less than a specific range (less than ±10 μm), and further making the peel strength between the intermediate layer and the two outer layers less than a specific range (less than 0.1 N / cm), it is possible to stabilize the interface between the formed intermediate layer and the two outer layers, and it is possible to peel the outer layer from the intermediate layer smoothly and quickly.

[0079] In the first aspect of the present invention, the thickness (X) of the intermediate layer [I] is 1 μm to 100 μm, and the ratio (Y / X) of the thickness (Y) of the two outer layers [II] to the thickness (X) of the intermediate layer [I] is 1 to 5, preferably 1 to 4.5, more preferably 1 to 4, and further preferably 1 to 3.5. Here, the thicknesses of the two outer layers [II] may be different, but are preferably the same.

[0080] By making the thickness ratio (Y / X) within the above range, a laminated film having an intermediate layer with small thickness fluctuations, good appearance, high conductivity, and excellent peelability between the intermediate layer and the two outer layers can be obtained.

[0081] On the other hand, if the thickness ratio (Y / X) deviates from the above range, there is a concern that only an intermediate layer with large thickness fluctuations, poor appearance such as flow unevenness and hole opening on the film, and poor conductivity can be obtained, and only a laminated film with poor peelability between the intermediate layer and the two outer layers, such as unstable peeling of the outer layer and stick-slip (jamming) when peeling the outer layer from the laminated film, can be obtained.

[0082] The laminated film of the second aspect of the present invention has: an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1). The thickness fluctuations of the intermediate layer [I] are less than ±10 μm, and the surface wetting index of at least one side of the intermediate layer [I] is 30 dyne / cm or more.

[0083] According to the second aspect of the present invention, the following effects are achieved: It is possible to provide a laminated film having an intermediate layer with small thickness fluctuations, excellent coatability of an aqueous liquid, good appearance, high conductivity, and excellent peelability between the intermediate layer and the two outer layers. In addition, according to the present invention, the following effects are achieved: It is possible to provide a conductive film with small thickness fluctuations, excellent coatability, good appearance, and high conductivity.

[0084] The reason is not clear yet, but it is considered as follows.

[0085] It is considered that by making the thickness fluctuation of the intermediate layer smaller than a specific range (less than ±10 μm), it is possible to stabilize the interface between the formed intermediate layer and the two outer layers, and the outer layer can be peeled off from the intermediate layer smoothly and quickly.

[0086] In addition, it is considered that by making the surface wetting index of at least one side of the intermediate layer that can be a conductive film a specific value or more (30 dyne / cm or more), the interfacial surface tension of the intermediate layer can be made close to the surface tension of the aqueous liquid when coating the aqueous liquid on the intermediate layer, the contact angle when the aqueous liquid contacts the surface of the intermediate layer becomes smaller, and the aqueous liquid can be easily and uniformly coated on the surface of the intermediate layer.

[0087] Here, when the intermediate layer that can be a conductive film is used for the purpose of a current collector for a negative electrode, the aqueous coating for a negative electrode (for example, an aqueous coating for a negative electrode obtained by mixing a negative electrode active material, a binder, and an aqueous solvent) corresponds to the aqueous liquid.

[0088] In the second aspect of the present invention, the surface wetting index of at least one side of the intermediate layer [I] is 30 dyne / cm or more, preferably 31 dyne / cm or more, and more preferably 32 dyne / cm or more. It should be noted that the upper limit is not particularly limited, usually 60 dyne / cm, and preferably 50 dyne / cm.

[0089] The surface wetting index of at least one side of the intermediate layer [I] can be set by appropriately adjusting the type and amount of the resin contained in the resin composition (A) constituting the intermediate layer.

[0090] By making the wetting index a specific value or more (30 dyne / cm or more), the aqueous liquid is not easily repelled on the surface of the intermediate layer, and the aqueous liquid can be uniformly coated on the intermediate layer.

[0091] On the other hand, if the wetting index is less than a specific value (less than 30 dyne / cm), the aqueous liquid is repelled on the surface of the intermediate layer, unevenness is likely to occur, and there is a concern that the aqueous liquid cannot be uniformly coated on the intermediate layer.

[0092] It should be noted that the surface wetting index of at least one side of the intermediate layer [I] can be determined by the method described in the examples.

[0093] The laminated film in the third embodiment of the present invention has an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1). The intermediate layer [I] is a layer formed by multiple layers, and the surface wetting index of at least one surface layer (i-1) of the intermediate layer [I] is 30 dyne / cm or more.

[0094] According to the third embodiment of the present invention, the following effects are achieved: It is possible to provide a laminated film having an intermediate layer with excellent coating properties of an aqueous liquid, excellent mechanical properties such as elongation at break in tension, small thickness fluctuation, good appearance, high conductivity, and excellent peelability between the intermediate layer and the two outer layers. In addition, according to the present invention, the following effects are achieved: It is possible to provide a conductive film with excellent coating properties of an aqueous liquid, excellent mechanical properties such as elongation at break in tension, small thickness fluctuation, good appearance, and high conductivity.

[0095] The reason is not yet clear, but it is considered as follows.

[0096] It is considered that by forming the intermediate layer into a layer formed by multiple layers, even if a material with a low elongation rate is used for the middle layer (i-2) of the intermediate layer, the middle layer (i-2) is elongated in a manner following the surface layer (i-1) by laminating a material with a high elongation rate on at least one surface layer (i-1) of the intermediate layer. As a result, the elongation rate of the entire intermediate layer is increased, and thus mechanical properties such as elongation at break in tension can be obtained.

[0097] In addition, it is considered that by making the surface wetting index of at least one surface layer (i-1) of the intermediate layer that can be a conductive film a specific value or more (30 dyne / cm or more), the interfacial surface tension of the surface layer (i-1) of the intermediate layer can be made close to the surface tension of the aqueous liquid when an aqueous liquid is coated on at least one surface layer (i-1) of the intermediate layer. The contact angle when the aqueous liquid contacts the surface of the intermediate layer becomes smaller, and it is possible to easily coat the aqueous liquid uniformly on the surface of at least one surface layer (i-1) of the intermediate layer.

[0098] Here, when the intermediate layer that can be a conductive film is used for the purpose of a negative electrode current collector, the negative electrode aqueous coating (for example, a negative electrode aqueous coating obtained by mixing a negative electrode active material, a binder, and an aqueous solvent) corresponds to the aqueous liquid.

[0099] In the third aspect of the present invention, the surface wetting index of at least one surface layer (i - 1) of the intermediate layer [I] is 30 dyne / cm or more, preferably 31 dyne / cm or more, and more preferably 32 dyne / cm or more. It should be noted that the upper limit is not particularly limited and is usually 60 dyne / cm, preferably 50 dyne / cm.

[0100] The surface wetting index of at least one surface layer (i - 1) of the intermediate layer [I] can be set by appropriately adjusting the type and amount of the resin contained in the resin composition (A1) constituting at least one surface layer (i - 1) of the intermediate layer.

[0101] By making the wetting index a specific value or more (30 dyne / cm or more), the aqueous liquid is less likely to be repelled on the surface of at least one surface layer (i - 1) of the intermediate layer, and the aqueous liquid can be uniformly coated on at least one surface layer (i - 1) of the intermediate layer.

[0102] On the other hand, if the wetting index is less than the specific value (less than 30 dyne / cm), the aqueous liquid is repelled on the surface of at least one surface layer (i - 1) of the intermediate layer, unevenness is likely to occur, and there is a concern that the aqueous liquid cannot be uniformly coated on at least one surface layer (i - 1) of the intermediate layer.

[0103] It should be noted that the surface wetting index of at least one surface layer (i - 1) of the intermediate layer [I] can be obtained by the method described in the examples.

[0104] <Intermediate layer [I]>

[0105] (Thickness (X) of the intermediate layer [I])

[0106] In the laminated film of the first aspect of the present invention, the thickness (X) of the intermediate layer [I] is 1 μm to 100 μm, preferably 3 to 50 μm, more preferably 5 to 20 μm, further preferably 5 to 18 μm, and still more preferably 5 to 17 μm.

[0107] By making the thickness (X) of the intermediate layer [I] within the above range, the processability during film formation becomes good, and it is easy to obtain the mechanical strength as a film, and it can be particularly advantageously used for applications of conductive films that require weight reduction and thinning.

[0108] It should be noted that the thickness (X) of the intermediate layer [I] can be obtained by the method described in the examples.

[0109] (Thickness fluctuation of the intermediate layer [I])

[0110] In the laminated film of the first mode, the thickness fluctuation of the intermediate layer [I] is less than ±10 μm, preferably ±8 μm or less, more preferably ±5 μm or less, and still more preferably ±3 μm or less.

[0111] By making the thickness fluctuation of the intermediate layer [I] within the above range, it is easy to obtain a laminated film in which the interface between the formed intermediate layer and the two outer layers is stabilized, the appearance of the intermediate layer is good, the peeling of the outer layer is stabilized when the outer layer is peeled from the laminated film, and the peelability between the intermediate layer and the two outer layers is excellent.

[0112] The thickness fluctuation is usually expressed in %, but in the present invention, it is expressed in μm.

[0113] It should be noted that the thickness fluctuation of the intermediate layer [I] can be obtained by the method described in the examples.

[0114] (Peeling strength between the intermediate layer and the two outer layers)

[0115] When the T-peeling is carried out under the conditions of a peeling speed of 100 mm / min at a temperature of 25 °C for the laminated film of the first mode of the present invention, the peeling strength between the intermediate layer and the two outer layers is less than 0.1 N / cm. The peeling strength between the intermediate layer and the two outer layers is preferably 0.08 N / cm or less, more preferably 0.06 N / cm or less, still more preferably 0.04 N / cm or less, and even more preferably 0.035 N / cm or less. It should be noted that the lower limit is not particularly limited, preferably 0.001 N / cm, more preferably 0.005 N / cm, and still more preferably 0.01 N / cm.

[0116] By making the peeling strength between the intermediate layer and the two outer layers within the above range, not only the peeling defects such as a part of the two outer layers adhering to the intermediate layer are suppressed, but also the outer layer can be peeled from the intermediate layer smoothly and quickly. Thereby, the surface quality of the conductive film can be improved, and further, the productivity of the conductive film, the current collector using the conductive film, and the battery using the conductive film can be improved.

[0117] In addition, by making the peeling strength between the intermediate layer and the two outer layers within the above range, the peeling defect that the two outer layers are peeled from the intermediate layer during the winding of the laminated film can be suppressed. On the other hand, the peeling defect that a part of the two outer layers adheres to the intermediate layer when the outer layer is peeled from the laminated film can also be prevented.

[0118] It should be noted that the peeling strength between the intermediate layer and the two outer layers can be obtained by the method described in the examples.

[0119] (Thickness fluctuation of the intermediate layer [I])

[0120] In the laminated film of the second mode of the present invention, the thickness fluctuation of the intermediate layer [I] is less than ±10 μm, preferably ±8 μm or less, more preferably ±5 μm or less, and further preferably ±3 μm or less.

[0121] By making the thickness fluctuation of the intermediate layer [I] within the above range, it is easy to obtain a laminated film in which the interface between the formed intermediate layer and the two outer layers is stabilized, the appearance of the intermediate layer is good, the peeling of the outer layer is stabilized when the outer layer is peeled from the laminated film, and the peelability between the intermediate layer and the two outer layers is excellent.

[0122] The thickness fluctuation is usually expressed in %, but in the present invention, it is expressed in μm.

[0123] It should be noted that the thickness fluctuation of the intermediate layer [I] can be obtained by the method described in the examples.

[0124] (Thickness (X) of the intermediate layer [I])

[0125] In the laminated film of the second mode, the thickness (X) of the intermediate layer [I] is preferably 1 μm to 200 μm, more preferably 3 to 180 μm, further preferably 5 to 150 μm, still further preferably 5 to 100 μm, and still further preferably 5 to 80 μm.

[0126] By making the thickness (X) of the intermediate layer [I] within the above range, the processability during film formation is good, and it is easy to obtain the mechanical strength of the film, and it can be particularly advantageously used for applications requiring light weight and thin film of conductive films.

[0127] It should be noted that the thickness (X) of the intermediate layer [I] can be obtained by the method described in the examples.

[0128] (Thickness ratio (Y / X) of the two outer layers [II] to the intermediate layer [I])

[0129] In the laminated film of the second mode, the ratio (Y / X) of the thickness (Y) of each layer of the two outer layers [II] to the thickness (X) of the intermediate layer [I] is preferably 1 to 5, more preferably 1 to 4.5, further preferably 1 to 4, and still further preferably 1 to 3.5. Here, the thickness of each layer of the two outer layers [II] can be different, but it is preferably the same.

[0130] It should be noted that the thickness of the intermediate layer [I] and the thickness of the two outer layers [II] can be set by appropriately adjusting the extrusion amount or extrusion speed of the resin compositions (A) and (B), the temperature of the casting roll or the traction speed, the lip die gap of the T-die, the resin temperature during extrusion, etc.

[0131] By making the thickness ratio (Y / X) within the above range, it is easy to obtain an intermediate layer with small thickness fluctuations, good appearance, and high conductivity, and the laminate film has excellent peelability between the intermediate layer and the two outer layers.

[0132] On the other hand, if the thickness ratio (Y / X) deviates from the above range, there is a concern that only an intermediate layer with large thickness fluctuations, uneven flow, opening, etc. on the film surface, poor appearance, and poor conductivity can be obtained, and only a laminate film with poor peelability between the intermediate layer and the two outer layers, such as unstable peeling of the outer layer when peeling the outer layer from the laminate film and sticking (jamming), can be obtained.

[0133] (Peel strength between the intermediate layer [I] and the two outer layers [II])

[0134] For the laminate film of the second aspect of the present invention, when performing T-peeling at a peeling speed of 100 mm / min in an environment of 25°C, the peel strength between the intermediate layer [I] and the two outer layers [II] is preferably less than 0.1 N / cm, more preferably 0.08 N / cm or less, further preferably 0.06 N / cm or less, still further preferably 0.04 N / cm or less, and even further preferably 0.035 N / cm or less. It should be noted that the lower limit is not particularly limited, preferably 0.001 N / cm, more preferably 0.005 N / cm, and further preferably 0.01 N / cm.

[0135] It should be noted that the peel strength between the intermediate layer [I] and the two outer layers [II] can be set by, for example, making the ratio (Y / X) of the thickness (Y) of the two outer layers [II] to the thickness (X) of the intermediate layer [I] 1 to 5, and appropriately adjusting the type of the conductive filler (a2), the type of the resin constituting the intermediate layer [I], the type of the resin constituting the two outer layers [II], the melt viscosity of the resin constituting the intermediate layer [I], and the melt viscosity of the resin constituting the two outer layers [II].

[0136] By making the peel strength between the intermediate layer and the two outer layers within the above range, not only is the peeling defect such as a part of the two outer layers adhering to the intermediate layer suppressed, but also the outer layer can be peeled off from the intermediate layer smoothly and quickly. Thereby, the surface quality of the intermediate layer that can be a conductive film can be improved, and further, the productivity of the conductive film, the current collector using the conductive film, and the battery using the conductive film can be improved.

[0137] In addition, by making the peel strength between the intermediate layer and the two outer layers within the above range, the peeling defect of the two outer layers peeling off from the intermediate layer during the winding of the laminate film can be suppressed. On the other hand, it can also prevent the peeling defect such as a part of the two outer layers adhering to the intermediate layer when peeling the outer layer from the laminate film.

[0138] It should be noted that the peel strength between the intermediate layer and the two outer layers can be obtained by the method described in the examples.

[0139] (Layer structure of the intermediate layer [I])

[0140] The intermediate layer [I] of the third embodiment of the present invention is a layer formed by a plurality of layers composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2).

[0141] The layer structure of the intermediate layer [I] is not particularly limited as long as it is a layer formed by a plurality of layers, and a structure in which two or more surface layers (i-1) are laminated on at least one side of the middle layer (i-2) is preferred. As the layer structure of the intermediate layer [I], for example, the following methods can be cited. The total number of layers forming the middle layer (i-2) can be appropriately adjusted according to the use and purpose.

[0142] · Surface layer (i-1) / Middle layer (i-2)

[0143] · Surface layer (i-1) / Middle layer (i-2) / Surface layer (i-1)

[0144] The layer structure of the intermediate layer [I] in the present invention is preferably a layer structure formed by two layers of surface layer (i-1) / middle layer (i-2), or a layer structure formed by three layers of surface layer (i-1) / middle layer (i-2) / surface layer (i-1), and more preferably a layer structure formed by three layers of surface layer (i-1) / middle layer (i-2) / surface layer (i-1).

[0145] It should be noted that when the intermediate layer [I] is composed of two layers, since it is the same as the structure obtained by removing one surface layer (i-1) from the structure in which the intermediate layer [I] is composed of three layers, even in the case of a two-layer structure, for convenience, the middle layer (i-2) is directly referred to as the middle layer.

[0146] (Surface layer (i-1))

[0147] From the viewpoint of improving the coatability of the aqueous liquid on the intermediate layer [I], at least one surface layer (i-1) of the intermediate layer [I] is preferably composed of a resin composition (A1) containing a thermoplastic resin (a1), a conductive filler (a2), and a carboxylic acid-modified polyolefin resin (a3).

[0148] (Middle layer (i-2))

[0149] On the other hand, from the viewpoint of obtaining mechanical properties such as elongation at break, the middle layer (i-2) of the intermediate layer [I] is preferably composed of a resin composition (A2) containing a thermoplastic resin (a1) and a conductive filler (a2) and substantially not containing a carboxylic acid-modified polyolefin resin (a3).

[0150] Here, "substantially free of" includes not only completely free of, i.e., 0% by mass, but also cases where the content is, for example, 0.05% by mass or less (in some cases, it may be 0.03% by mass or less, 0.01% by mass or less), that is, the content is insufficient to reach the meaning of containing.

[0151] (Volume resistivity of the intermediate layer [I])

[0152] In the laminated film, the volume resistivity of the intermediate layer [I] is preferably 500 Ω·cm or less, more preferably 300 Ω·cm or less, further preferably 200 Ω·cm or less, still further preferably 100 Ω·cm or less, and even more preferably 50 Ω·cm or less.

[0153] By making the volume resistivity of the intermediate layer [I] within the above range, a laminated film having an intermediate layer with high conductivity can be obtained, and the intermediate layer obtained by peeling off the two outer layers from the laminated film is particularly advantageously used for the purpose of a conductive film.

[0154] It should be noted that the volume resistivity of the intermediate layer [I] can be obtained by the method described in the examples.

[0155] (Resin composition (A))

[0156] The intermediate layer [I] is a layer composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2). In the second mode, furthermore, the resin composition (A) preferably contains a carboxylic acid-modified polyolefin resin (a3).

[0157] (Thermoplastic resin (a1))

[0158] In the third mode, the resin composition (A) constituting the entire intermediate layer [I] formed of multiple layers contains a thermoplastic resin (a1). When the intermediate layer [I] is a layer formed of 2 or 3 layers, the resin composition (A1) constituting the surface layer (i−1) and the resin composition (A2) constituting the middle layer (i−2) contain a thermoplastic resin (a1).

[0159] The thermoplastic resin (a1) is not particularly limited, and various thermoplastic resins can be used. Among thermoplastic resins, from the viewpoint of ensuring the mechanical strength of the film, polyolefin resins are preferred.

[0160] As polyolefin resins, for example, homopolymers of α-olefins having about 2 to 8 carbon atoms such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, etc.; copolymers of these α-olefins and other α-olefins having about 2 to 12 carbon atoms such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, etc., vinyl compounds such as vinyl acetate, acrylic acid, methacrylic acid, acrylate, methacrylate, styrene, vinyl chloride, etc.; graft polymers obtained by grafting the above vinyl compounds, etc. onto the homopolymers and copolymers of the above α-olefins. Among them, from the viewpoint of stabilizing the interface between the formed intermediate layer and the two outer layers, a polypropylene-based resin or a polyethylene-based resin is preferred, and a polypropylene-based resin is more preferred.

[0161] The polypropylene-based resin can be a propylene homopolymer (homopolymer of propylene), or a copolymer of propylene and an olefin having 2 to 20 carbon atoms. One type or two or more types of olefins copolymerizable with propylene can be used. Specific examples of the propylene copolymer include propylene-ethylene copolymer, propylene-1-butene copolymer, propylene-ethylene-1-butene copolymer, etc. Among them, from the viewpoint of the film-forming property of the intermediate layer, a propylene homopolymer is preferred.

[0162] The polyethylene-based resin can be an ethylene homopolymer (homopolymer of ethylene), or a resin copolymerized from ethylene and comonomer components such as α-olefins and vinyl monomers. Specific examples of the ethylene copolymer include ethylene-1-butene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, etc.

[0163] The isotactic pentad fraction representing the stereoregularity of the polypropylene-based resin is preferably 80 to 99%, more preferably 83 to 98%, and further preferably 85 to 97%.

[0164] If the isotactic pentad fraction is too low, there is a concern that the mechanical strength of the film will decrease. On the other hand, for the upper limit of the isotactic pentad fraction, it is currently defined by the upper limit value obtainable industrially, but in the future, when resins with higher regularity are developed at the industrial level, it will not be limited to this. The isotactic pentad fraction refers to the three-dimensional structure or its ratio in which, with respect to the main chain based on carbon-carbon bonds composed of any continuous 5 propylene units, 5 methyl groups as side chains are all in the same direction. According to 13It is determined by the pentad component units in the polypropylene molecular chain measured by the signals in the methyl region of the 13C-NMR spectrum. The assignment of the signals in the methyl region is based on A. Zambelli et al. (Macromol. 8, 687 (1975)).

[0165] In addition, Mw / Mn, which is a parameter representing the molecular weight distribution of the polypropylene-based resin, is preferably 1.5 or more, more preferably 2.0 or more. On the other hand, the upper limit is preferably 10.0 or less, more preferably 8.0 or less, and further preferably 6.0 or less. The smaller Mw / Mn is, the narrower the molecular weight distribution means. By making Mw / Mn 1.5 or more, sufficient extrusion moldability can be obtained, and it can be mass-produced industrially. On the other hand, by making Mw / Mn 10.0 or less, the mechanical strength as a film can be ensured. Mw represents the weight-average molecular weight, Mn represents the number-average molecular weight, and Mw / Mn is obtained by the GPC (gel permeation chromatography) method.

[0166] The melt flow rate (MFR) of the polypropylene-based resin is preferably 1.0 to 30 g / 10 min, more preferably 5.0 to 20 g / 10 min.

[0167] By making the melt flow rate (MFR) within the above range, even when the viscosity increases due to the filling of the conductive filler, sufficient melt viscosity is obtained during the molding process of the resin composition (A), and the mechanical strength as a film can be ensured.

[0168] It should be noted that the melt flow rate (MFR) is a value measured under the conditions of a temperature of 230 °C and a load of 2.16 kg in accordance with JIS K7210.

[0169] As the polypropylene-based resin, for example, commercially available products such as the trade names "NOVATEC PP", "WINTEC" (manufactured by Japan Polypropylene Corporation), "NOTIO", "TAFMER XR" (manufactured by Mitsui Chemicals, Inc.), "Zelas", "Thermorun" (manufactured by Mitsubishi Chemical Corporation), "Sumitomo Noblen", "Tafthren" (manufactured by Sumitomo Chemical Co., Ltd.), "Prime PP", "PrimeTPO" (manufactured by Prime Polymer Co., Ltd.), "Adflex", "Adsyl", "HMS-PP (PF814)" (manufactured by SunAllomer Co., Ltd.), and "VERSIFY", "INSPIRE" (manufactured by The Dow Chemical Company) can be used.

[0170] (Content of the thermoplastic resin (a1))

[0171] In the resin composition (A), the content of the thermoplastic resin (a1) in the first and second embodiments of the present invention is preferably 50 to 99% by mass, more preferably 60 to 98% by mass, and still more preferably 70 to 97% by mass.

[0172] By making the content of the thermoplastic resin (a1) within the above range, it is easy to obtain a laminated film with good dispersibility of the conductive filler (a2), ensuring the mechanical strength as a film, stabilizing the peeling of the outer layer when peeling the outer layer from the laminated film, and excellent peelability between the intermediate layer and the two outer layers.

[0173] In the third embodiment of the present invention, the resin composition (A) constituting the entire intermediate layer [I] formed of multiple layers contains the thermoplastic resin (a1).

[0174] In the resin composition (A), the content of the thermoplastic resin (a1) in the resin composition (A) is preferably 60 to 95% by mass, more preferably 65 to 90% by mass, and still more preferably 70 to 88% by mass.

[0175] By making the content of the thermoplastic resin (a1) in the resin composition (A) within the above range, it is easy to obtain a laminated film with good dispersibility of the conductive filler (a2), ensuring the mechanical strength as a film, stabilizing the peeling of the outer layer when peeling the outer layer from the laminated film, and excellent peelability between the intermediate layer and the two outer layers.

[0176] The resin composition (A1) constituting the surface layer (i-1) of the intermediate layer [I] contains the thermoplastic resin (a1).

[0177] In the resin composition (A1), the content of the thermoplastic resin (a1) in the resin composition (A1) is preferably 60 to 98% by mass, more preferably 65 to 95% by mass, and still more preferably 70 to 90% by mass.

[0178] By making the content of the thermoplastic resin (a1) in the resin composition (A1) within the above range, it is easy to obtain a laminated film with good dispersibility of the conductive filler (a2), ensuring the mechanical strength as a film, stabilizing the peeling of the outer layer when peeling the outer layer from the laminated film, and excellent peelability between the intermediate layer and the two outer layers.

[0179] The resin composition (A2) constituting the middle layer (i-2) of the intermediate layer [I] contains the thermoplastic resin (a1).

[0180] In the resin composition (A2), the content of the thermoplastic resin (a1) in the resin composition (A2) is preferably 60 to 99.5% by mass, more preferably 65 to 99% by mass, and still more preferably 70 to 98% by mass.

[0181] By making the content of the thermoplastic resin (a1) in the resin composition (A2) within the above range, it is easy to obtain an intermediate layer with good dispersibility of the conductive filler (a2), ensuring excellent mechanical properties such as mechanical strength and elongation at break as a film.

[0182] (Conductive filler (a2))

[0183] The resin composition (A) constituting the entire intermediate layer [I] formed of multiple layers contains a conductive filler (a2).

[0184] When the intermediate layer [I] is a layer formed of two or three layers, the resin composition (A1) constituting the surface layer (i - 1) and the resin composition (A2) constituting the middle layer (i - 2) contain a conductive filler (a2).

[0185] The conductive filler (a2) in the first and second aspects of the present invention is not particularly limited, and examples thereof include carbon fillers such as carbon black, carbon nanotubes, carbon nanofibers, graphite carbon, and carbon fibers; powdered or fibrous metals; metal oxides; metal nitrides; etc. Among them, carbon fillers are preferred, and at least one selected from carbon nanotubes and carbon black is more preferred. From the viewpoint of obtaining good conductivity even when the conductive filler contained in the resin composition (A) is small and easily making the peel strength between the intermediate layer and the two outer layers less than a specific range (less than 0.1 N / cm), carbon nanotubes are further preferred. On the other hand, from the viewpoint of economy, carbon black is preferred.

[0186] The conductive filler (a2) in the third aspect of the present invention is not particularly limited, and examples thereof include carbon fillers such as carbon black, carbon nanotubes, carbon nanofibers, graphite carbon, and carbon fibers; powdered or fibrous metals; metal oxides; metal nitrides; etc. Among them, carbon fillers are preferred, and at least one selected from carbon nanotubes and carbon black is more preferred.

[0187] From the viewpoint of easily obtaining good conductivity even in a small amount and easily making the peel strength between the intermediate layer and the two outer layers less than a specific range (less than 0.1 N / cm), the conductive filler contained in the resin composition (A) constituting the entire intermediate layer [I], the resin composition (A1) constituting the surface layer (i - 1), and the resin composition (A2) constituting the middle layer (i - 2) is further preferably carbon nanotubes. On the other hand, from the viewpoint of economy, carbon black is preferred.

[0188] In particular, from the viewpoint of obtaining an intermediate layer with excellent mechanical properties such as elongation at break, the conductive filler contained in the resin composition (A2) constituting the middle layer (i - 2) is preferably carbon nanotubes.

[0189] As the carbon nanotubes, they can be either single-walled carbon nanotubes or multi-walled carbon nanotubes. Additionally, the manufacturing method of the carbon nanotubes is not particularly limited, and any one of thermal decomposition methods such as thermal CVD, plasma CVD, arc discharge method, laser evaporation method, etc. can be used.

[0190] It should be noted that in the present invention, for example, the carbon nanotubes described in Japanese Patent Application Laid-Open No. 2018-127397 can be used.

[0191] On the other hand, as the carbon black, specifically, Ketjenblack; acetylene black; furnace black; channel black; carbon black by-produced when hydrocarbons are partially oxidized in the presence of hydrogen and oxygen to produce synthesis gas containing hydrogen and carbon monoxide, such as naphtha, or carbon black obtained by subjecting it to oxidation or reduction treatment, etc. are exemplified. Acetylene black and Ketjenblack are preferred. These carbon blacks can be used alone or in combination of two or more.

[0192] The carbon black is preferably in a particulate form with an aspect ratio of 1 to 5. It should be noted that in the case where the carbon black is in a particulate form, the aspect ratio refers to the value obtained by dividing the length of the major axis of the spherical component constituting the carbon black structure by the length of the minor axis of the spherical component. On the other hand, in the case where the carbon black is in a fibrous form, it refers to the value obtained by dividing the fiber length by the fiber diameter.

[0193] The average primary particle diameter of the carbon black is preferably 10 nm or more, more preferably 20 nm or more. On the other hand, the upper limit is preferably 60 nm or less, more preferably 50 nm or less. By making the average primary particle diameter of the carbon black 10 nm or more, its dispersibility in the resin composition (A) can be made good, and agglomerates caused by undispersed carbon black are not easily generated. On the other hand, by making the average primary particle diameter of the carbon black 60 nm or less, the volume resistivity as an index of conductivity when dispersed in the resin composition (A) can be reduced, and good conductivity can be obtained.

[0194] The lower limit of the DBP oil absorption of the carbon black is preferably 50 ml / 100 g or more, more preferably 100 ml / 100 g or more. On the other hand, the upper limit is preferably 750 ml / 100 g or less, more preferably 400 ml / 100 g or less. When the DBP oil absorption is 50 ml / 100 g or more, the structure is larger and good conductivity can be obtained. On the other hand, when the DBP oil absorption is 750 ml / 100 g or less, its dispersibility in the resin composition (A) can be made good, and agglomerates caused by undispersed carbon black are not easily generated.

[0195] It should be noted that the DBP oil absorption is an index indicating the degree of the structure, that is, the structure formed by chemical or physical bonding and aggregation of particles, by the amount of dibutyl phthalate (DBP) used to fill the voids between carbon black particles, and is the amount (ml) of DBP that can be contained in every 100 g of carbon black.

[0196] As the carbon black, for example, commercially available products such as "BLACK PEARLS", "VULCAN", "STERLING" (manufactured by Cabot Corporation), "Ketjenblack EC" (manufactured by LION SPECIALTY CHEMICALS), "DENKA BLACK" (manufactured by Denki Kagaku Kogyo Co., Ltd.), "TOCABLACK" (manufactured by Tokai Carbon Co., Ltd.), "Asahi Carbon Black" (manufactured by Asahi Carbon Co., Ltd.), and "Mitsubishi Carbon Black" (manufactured by Mitsubishi Chemical Corporation) can be used.

[0197] (Content of the conductive filler (a2))

[0198] In the first and second aspects of the present invention, the content of the conductive filler (a2) in the resin composition (A) is preferably 0.1 to 50% by mass, more preferably 1 to 40% by mass, and further preferably 2 to 30% by mass.

[0199] By making the content of the conductive filler (a2) within the above range, good dispersibility in the resin composition (A) can be achieved, agglomerates caused by non-dispersion of the conductive filler are less likely to occur, and a laminated film having an intermediate layer with good appearance and high conductivity can be easily obtained.

[0200] Among them, when the conductive filler (a2) is a carbon nanotube, the content of the carbon nanotube in the resin composition (A) is preferably 0.1 to 30% by mass, more preferably 0.3 to 20% by mass, further preferably 0.5 to 10% by mass, and still more preferably 1 to 8% by mass.

[0201] In addition, when the conductive filler (a2) is carbon black, the content of the carbon black in the resin composition (A) is preferably 1 to 50% by mass, more preferably 3 to 40% by mass, further preferably 5 to 35% by mass, still more preferably 5 to 30% by mass, and still more preferably 5 to 25% by mass.

[0202] In the third aspect of the present invention, the resin composition (A) constituting the entire intermediate layer [I] formed of multiple layers contains the conductive filler (a2).

[0203] In the resin composition (A), the content of the conductive filler (a2) in the resin composition (A) is preferably 0.1% by mass to 50% by mass, more preferably 1 to 40% by mass, further preferably 2 to 30% by mass, still more preferably 2 to 20% by mass, and still more preferably 3 to 15% by mass.

[0204] By making the content of the conductive filler (a2) in the resin composition (A) within the above range, good dispersibility of the resin composition (A) can be achieved, agglomerates caused by non-dispersion of the conductive filler are less likely to occur, and a laminated film with an intermediate layer having good appearance and high conductivity can be easily obtained.

[0205] Among them, when the conductive filler (a2) contained in the resin composition (A) is a carbon nanotube, the content of the carbon nanotube in the resin composition (A) is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, further preferably 1 to 10% by mass, and still more preferably 1.5 to 8% by mass.

[0206] In addition, when the conductive filler (a2) contained in the resin composition (A) is carbon black, the content of the carbon black in the resin composition (A) is preferably 1 to 40% by mass, more preferably 3 to 35% by mass, further preferably 5 to 30% by mass, and still more preferably 7 to 20% by mass.

[0207] In the third aspect of the present invention, when the intermediate layer [I] is a layer formed of two or three layers, the resin composition (A1) constituting the surface layer (i-1) contains the conductive filler (a2).

[0208] In the resin composition (A1), the content of the conductive filler (a2) in the resin composition (A1) is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, further preferably 1 to 10% by mass, and still more preferably 1.5 to 8% by mass.

[0209] By making the content of the conductive filler (a2) in the resin composition (A1) within the above range, good dispersibility in the resin composition (A1) can be achieved, agglomerates caused by non-dispersion of the conductive filler are less likely to occur, and a laminated film with an intermediate layer having good appearance and high conductivity can be easily obtained.

[0210] Among them, when the conductive filler (a2) contained in the resin composition (A1) is a carbon nanotube, the content of the carbon nanotube in the resin composition (A1) is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, further preferably 1 to 10% by mass, and still more preferably 1.5 to 8% by mass.

[0211] In addition, when the conductive filler (a2) contained in the resin composition (A1) is carbon black, the content of the carbon black in the resin composition (A1) is preferably 1 to 40% by mass, more preferably 3 to 35% by mass, further preferably 5 to 30% by mass, and still more preferably 7 to 20% by mass.

[0212] In the third aspect of the present invention, when the intermediate layer [I] is a layer formed of two or three layers, the resin composition (A2) constituting the intermediate layer (i-2) contains a conductive filler (a2).

[0213] In the resin composition (A2), the content of the conductive filler (a2) in the resin composition (A2) is preferably 1 to 40% by mass, more preferably 1.5 to 35% by mass, still more preferably 2 to 30% by mass, and even more preferably 3 to 25% by mass.

[0214] By making the content of the conductive filler (a2) in the resin composition (A2) within the above range, it is possible to achieve good dispersibility in the resin composition (A2), and it is not easy to generate agglomerates caused by non-dispersion of the conductive filler. It is easy to obtain a laminated film with an intermediate layer having good appearance and high conductivity, and it is easy to obtain an intermediate layer with excellent mechanical properties such as elongation at break.

[0215] Among them, when the conductive filler (a2) contained in the resin composition (A2) is a carbon nanotube, the content of the carbon nanotube in the resin composition (A2) is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, still more preferably 1 to 10% by mass, and even more preferably 1.5 to 8% by mass.

[0216] In addition, when the conductive filler (a2) contained in the resin composition (A2) is carbon black, the content of the carbon black in the resin composition (A2) is preferably 1 to 40% by mass, more preferably 1.5 to 35% by mass, still more preferably 2 to 30% by mass, and even more preferably 3 to 25% by mass.

[0217] (Carboxylic acid-modified polyolefin resin (a3))

[0218] In the second aspect of the present invention, from the viewpoint of improving the coatability of the aqueous liquid on the intermediate layer [I], the resin composition (A) preferably contains a carboxylic acid-modified polyolefin resin (a3).

[0219] The carboxylic acid-modified polyolefin resin (a3) is a resin obtained by subjecting a polyolefin resin to carboxylic acid modification.

[0220] The polyolefin resin to be carboxylic acid-modified may be the same resin as the polyolefin resin described as the thermoplastic resin (a1).

[0221] Examples of the carboxylic acid compound used in the carboxylic acid modification include acid anhydrides such as maleic anhydride, phthalic anhydride, acetic anhydride, and succinic anhydride, methacrylic acid, maleic acid, and acrylic acid. Among them, at least one selected from maleic anhydride, methacrylic acid, maleic acid, and acrylic acid is preferred, and maleic anhydride is more preferred.

[0222] The carboxylic acid-modified polyolefin resin (a3) can be formed by copolymerizing a raw material monomer of a polyolefin resin with a carboxylic acid compound, or can be formed by adding a carboxylic acid compound to a polyolefin resin.

[0223] As the carboxylic acid-modified polyolefin resin (a3), a maleic acid-modified polyolefin resin is preferred, a maleic acid-modified polypropylene resin or a maleic acid-modified polyethylene resin is more preferred, and a maleic acid-modified polypropylene resin is further preferred.

[0224] It should be noted that the polyolefin resin used in the carboxylic acid-modified polyolefin resin (a3) and the polyolefin resin used in the thermoplastic resin (a1) may be the same or different.

[0225] From the viewpoint of improving the coatability of the aqueous liquid on the intermediate layer [I], the acid value of the carboxylic acid-modified polyolefin resin (a3) is preferably 1 to 70 mgKOH / g, more preferably 10 to 65 mgKOH / g, and further preferably 20 to 60 mgKOH / g.

[0226] By making the acid value of the carboxylic acid-modified polyolefin resin (a3) within the above range, the surface wetting index of at least one side of the intermediate layer [I] can be made to be a specific value or more, and the aqueous liquid can be easily and uniformly coated on the surface of the intermediate layer [I].

[0227] As the carboxylic acid-modified polyolefin resin (a3), for example, commercially available products such as "UMEX 1001" and "UMEX1010" (manufactured by Sanyo Chemical Industries, Ltd.) can be used.

[0228] In the resin composition (A), the content of the carboxylic acid-modified polyolefin resin (a3) is preferably 5% by mass to 50% by mass, more preferably 5 to 40% by mass, further preferably 5 to 30% by mass, and even more preferably 7 to 25% by mass.

[0229] By making the content of the carboxylic acid-modified polyolefin resin (a3) within the above range, the surface wetting index of at least one side of the intermediate layer [I] can be made to be a specific value or more, and the aqueous liquid can be easily and uniformly coated on the surface of the intermediate layer [I].

[0230] In the third aspect of the present invention, from the viewpoint of improving the coatability of the aqueous liquid on the intermediate layer [I], the resin composition (A1) constituting the surface layer (i-1) of the intermediate layer [I] preferably contains a carboxylic acid-modified polyolefin resin (a3).

[0231] The carboxylic acid-modified polyolefin resin (a3) is a resin obtained by subjecting a polyolefin resin to carboxylic acid modification.

[0232] As a carboxylic acid-modified polyolefin resin, it is the same as the carboxylic acid-modified polyolefin resin described in the second method.

[0233] The resin composition (A1) constituting the surface layer (i-1) of the intermediate layer [I] preferably contains a carboxylic acid-modified polyolefin resin (a3).

[0234] In the resin composition (A1), the content of the carboxylic acid-modified polyolefin resin (a3) in the resin composition (A1) is preferably 5% by mass to 50% by mass, more preferably 5 to 40% by mass, still more preferably 5 to 30% by mass, and even more preferably 7 to 25% by mass.

[0235] By making the content of the carboxylic acid-modified polyolefin resin (a3) within the above range, the surface wetting index of at least one surface layer (i-1) of the intermediate layer [I] can be made a specific value or more, and it is possible to easily coat the aqueous liquid uniformly on the surface of the intermediate layer [I].

[0236] (Additive)

[0237] In the resin composition (A), additives other than the thermoplastic resin (a1) and the conductive filler (a2) can be contained as needed within the range that does not hinder the properties of the intermediate layer [I]. In the resin composition (A), various additives can be contained as needed within the range that does not hinder the properties of the intermediate layer [I] in addition to the thermoplastic resin (a1) and the conductive filler (a2), and further preferably the carboxylic acid-modified polyolefin resin (a3). Alternatively, in the resin composition (A) constituting the entire intermediate layer [I] formed of multiple layers, the resin composition (A1) constituting the surface layer (i-1) of the intermediate layer [I], and the resin composition (A2) constituting the middle layer (i-2) of the intermediate layer [I], various additives can be contained as needed within the range that does not hinder the properties of the intermediate layer [I].

[0238] Examples of the additives include inorganic particles such as silica, talc, kaolin, and calcium carbonate, pigments such as titanium oxide and carbon black, flame retardants, weather resistance stabilizers, heat stabilizers, antistatic agents, melt viscosity improvers, crosslinking agents, lubricants, nucleating agents, plasticizers, anti-aging agents, antioxidants, light stabilizers, ultraviolet absorbers, neutralizing agents, antifogging agents, anti-blocking agents, slip agents, and colorants.

[0239] When using additives, their content in the resin composition (A) is usually 30% by mass or less, preferably 0.0001 to 20% by mass, more preferably 0.001 to 15% by mass, and still more preferably 0.01 to 10% by mass.

[0240] (Tensile elongation at break of the intermediate layer [I])

[0241] In the laminated film of the third aspect of the present invention, the elongation at break in the machine direction (MD) of the intermediate layer [I] is preferably 100% or more, more preferably 120% or more, further preferably 150% or more, still further preferably 200% or more, still further preferably 250% or more, and still further preferably 300% or more. Here, the upper limit value of the elongation at break is not particularly limited, and is usually 500% or less, preferably 400% or less.

[0242] It should be noted that the elongation at break in the machine direction (MD) of the intermediate layer [I] can be obtained by the method described in the examples.

[0243] (Thickness fluctuation of the intermediate layer [I])

[0244] In the laminated film of the third aspect of the present invention, the thickness fluctuation of the intermediate layer [I] is preferably less than ±10 μm, more preferably ±8 μm or less, further preferably ±5 μm or less, and still further preferably ±3 μm or less.

[0245] By making the thickness fluctuation of the intermediate layer [I] within the above range, it is easy to obtain a laminated film with stabilized interfaces between the formed intermediate layer and the two outer layers, good appearance of the intermediate layer, stabilized peeling of the outer layer when peeling the outer layer from the laminated film, and excellent peelability between the intermediate layer and the two outer layers.

[0246] The thickness fluctuation is usually expressed in %, but in the present invention, it is expressed in μm.

[0247] It should be noted that the thickness fluctuation of the intermediate layer [I] can be obtained by the method described in the examples.

[0248] (Thickness (X) of the intermediate layer [I])

[0249] In the laminated film of the third aspect of the present invention, the thickness (X) of the intermediate layer [I] is preferably 1 μm to 200 μm, more preferably 3 to 180 μm, further preferably 5 to 150 μm, still further preferably 5 to 100 μm, and still further preferably 5 to 80 μm.

[0250] By making the thickness (X) of the intermediate layer [I] within the above range, the processability during film formation is good, the mechanical strength of the film is easily obtained, and it can be particularly advantageously used for applications requiring lightweight and thin conductive films.

[0251] It should be noted that the thickness (X) of the intermediate layer [I] can be obtained by the method described in the examples.

[0252] (Thickness of the surface layer (i - 1))

[0253] In the intermediate layer [I] of the third mode of the present invention, the thickness of the surface layer (i - 1) is preferably 1 to 80 μm, more preferably 1.5 to 50 μm, further preferably 2 to 30 μm, and still further preferably 3 to 25 μm.

[0254] By making the thickness of the surface layer (i - 1) within the above range, the processability during film formation is good, and it is easy to obtain the mechanical strength as a film.

[0255] It should be noted that the surface layer (i - 1) can be obtained by the method described in the examples.

[0256] (Thickness of the intermediate layer (i - 2))

[0257] In the intermediate layer [I] of the third mode of the present invention, the thickness of the intermediate layer (i - 2) is preferably 2 to 160 μm, more preferably 3 to 100 μm, further preferably 4 to 60 μm, and still further preferably 6 to 50 μm.

[0258] By making the thickness of the intermediate layer (i - 2) within the above range, the processability during film formation is good, and it is easy to obtain an intermediate layer with excellent mechanical properties such as elongation at break.

[0259] It should be noted that the intermediate layer (i - 2) can be obtained by the method described in the examples.

[0260] (Thickness ratio of the intermediate layer (i - 2) to the surface layer (i - 1))

[0261] In the intermediate layer [I], from the aspects of film appearance and mechanical properties, the thickness ratio of the intermediate layer (i - 2) to the surface layer (i - 1) ((i - 2) / (i - 1)) is preferably 0.5 to 20, more preferably 0.75 to 10, further preferably 1.0 to 8, and still further preferably 1.2 to 5. Here, the thicknesses of the respective layers of the two surface layers (i - 1) can be different, but are preferably the same. The above thickness ratio can be adjusted by appropriately adjusting the extrusion amounts of the surface layer and the intermediate layer.

[0262] In addition, if within the above range, the film appearance and mechanical properties are good, and thus it is preferred.

[0263] (Thickness ratio (Y / X) of the two outer layers [II] to the intermediate layer [I])

[0264] In the laminated film of the third mode of the present invention, the ratio (Y / X) of the thickness (Y) of each layer of the two outer layers [II] to the thickness (X) of the intermediate layer [I] is preferably 1 to 5, more preferably 1 to 4.5, further preferably 1 to 4, and still further preferably 1 to 3.5. Here, the thicknesses of the respective layers of the two outer layers [II] can be different, but are preferably the same.

[0265] It should be noted that the thickness of the intermediate layer [I] and the thicknesses of the two outer layers [II] can be set by appropriately adjusting the extrusion amounts or extrusion speeds of the resin compositions (A) and (B), the temperature of the casting roll or the pulling speed, the lip die gap of the T-die, the resin temperature during extrusion, and the like.

[0266] By making the thickness ratio (Y / X) within the above range, it is easy to obtain a laminated film having an intermediate layer with small thickness fluctuations, good appearance, and high conductivity, and excellent peelability between the intermediate layer and the two outer layers.

[0267] On the other hand, if the thickness ratio (Y / X) deviates from the above range, it is feared that only an intermediate layer with large thickness fluctuations, uneven flow appearance, such as opening holes, poor appearance, and poor conductivity can be obtained, and only a laminated film with poor peelability between the intermediate layer and the two outer layers, such as unstable peeling of the outer layer when peeling the outer layer from the laminated film and resulting in stick-slip (jamming), can be obtained.

[0268] (Peel strength between the intermediate layer [I] and the two outer layers [II])

[0269] The peel strength between the intermediate layer [I] and the two outer layers [II] of the laminated film of the third aspect of the present invention during T-peeling at a peel speed of 100 mm / min in an environment at a temperature of 25°C is preferably less than 0.1 N / cm, more preferably 0.08 N / cm or less, further preferably 0.06 N / cm or less, still further preferably 0.04 N / cm or less, and still further preferably 0.035 N / cm or less. It should be noted that the lower limit is not particularly limited, and is preferably 0.001 N / cm, more preferably 0.005 N / cm, and further preferably 0.01 N / cm.

[0270] It should be noted that the peel strength between the intermediate layer [I] and the two outer layers [II] can be set by making the ratio (Y / X) of the thickness (Y) of the two outer layers [II] to the thickness (X) of the intermediate layer [I] be, for example, 1 to 5, and appropriately adjusting the type of the conductive filler (a2), the type of the resin constituting the intermediate layer [I], the type of the resin constituting the two outer layers [II], the melt viscosity of the resin constituting the intermediate layer [I], and the melt viscosity of the resin constituting the two outer layers [II].

[0271] By making the peel strength between the intermediate layer and the two outer layers within the above range, not only the peeling defects such as a part of the two outer layers adhering to the intermediate layer are suppressed, but also the outer layer can be peeled from the intermediate layer smoothly and quickly. Thereby, the surface quality of the intermediate layer that can be a conductive film can be improved, and further, the productivity of the conductive film, the current collector using the conductive film, and the battery using the conductive film can be improved.

[0272] In addition, by making the peel strength between the intermediate layer and the two outer layers within the above range, it is possible to suppress the defect that the two outer layers peel off from the intermediate layer during the winding of the laminated film. On the other hand, it is also possible to prevent the defect that a part of the two outer layers adheres to the intermediate layer or the like during the peeling of the outer layer from the laminated film.

[0273] It should be noted that the peel strength between the intermediate layer and the two outer layers can be obtained by the method described in the examples.

[0274] (Volume resistivity of the intermediate layer [I])

[0275] In the laminated film of the third aspect of the present invention, the volume resistivity of the intermediate layer [I] is preferably 500 Ω·cm or less, more preferably 300 Ω·cm or less, further preferably 200 Ω·cm or less, still more preferably 100 Ω·cm or less, and even more preferably 80 Ω·cm or less.

[0276] By making the volume resistivity of the intermediate layer [I] within the above range, a laminated film having an intermediate layer with high conductivity can be obtained, and the intermediate layer obtained by peeling off the two outer layers from the laminated film can be particularly advantageously used for the use of a conductive film.

[0277] It should be noted that the volume resistivity of the intermediate layer [I] can be obtained by the method described in the examples.

[0278] <Two outer layers [II]>

[0279] The two outer layers [II] can function as a protective film for protecting the intermediate layer [I], that is, the conductive film, until use without peeling.

[0280] (Thickness (Y) of the two outer layers [II])

[0281] In the laminated film, the thickness (Y) of the two outer layers [II] is preferably greater than 5 μm and 150 μm or less, more preferably 10 to 150 μm, further preferably 20 to 130 μm, and still more preferably 25 to 100 μm. Here, the thicknesses of the two outer layers [II] can be different, but are preferably the same.

[0282] By making the thickness of the two outer layers [II] within the above range, it is easy to stably form the interface between the intermediate layer and the two outer layers, the appearance of the intermediate layer becomes good, the peeling of the outer layer is stable when peeling the outer layer from the laminated film, and the laminated film has excellent peelability between the intermediate layer and the two outer layers.

[0283] It should be noted that the thickness (Y) of the two outer layers [II] can be obtained by the method described in the examples.

[0284] (Resin composition (B))

[0285] The two outer layers [II] are layers made of a resin composition (B) containing a thermoplastic resin (b1).

[0286] (Thermoplastic resin (b1))

[0287] The thermoplastic resin (b1) is not particularly limited. From the viewpoints of stable peeling of the outer layer when peeling the outer layer from the laminated film and good peelability between the intermediate layer and the two outer layers, it is preferably at least one selected from polyester resins, polycarbonate resins, and polystyrene resins.

[0288] In particular, when using a polyolefin resin (preferably a polypropylene resin) as the thermoplastic resin (a1) constituting the intermediate layer [I] or at least one surface layer (i-1) thereof, the thermoplastic resin (b1) is preferably at least one selected from polyester resins, polycarbonate resins, and polystyrene resins, and more preferably a polyester resin.

[0289] (Additive)

[0290] The resin composition (A) may contain additives other than the thermoplastic resin (b1) as needed within a range that does not hinder the properties of the two outer layers [II]. Examples of the additives include inorganic particles such as silica, talc, kaolin, and calcium carbonate, pigments such as titanium oxide and carbon black, flame retardants, weather resistance stabilizers, heat stabilizers, antistatic agents, melt viscosity improvers, crosslinking agents, lubricants, nucleating agents, plasticizers, anti-aging agents, antioxidants, light stabilizers, ultraviolet absorbers, neutralizing agents, antifogging agents, anti-blocking agents, slip agents, colorants, etc.

[0291] When using additives, their content in the resin composition (B) is usually 30% by mass or less, preferably 0.0001 to 20% by mass, more preferably 0.001 to 15% by mass, and further preferably 0.01 to 10% by mass.

[0292] (Layer constitution of the laminated film)

[0293] The laminated film in the present invention is not particularly limited as long as it is constituted by laminating outer layers [II] on both sides of the intermediate layer [I], and it may also have a constitution of four or more layers in which another layer [III] is laminated on at least one of the two outer layers [II] within a range that does not impair the effects of the present invention. Specific examples of the other layer [III] include a strength retention layer, a heat resistant layer, an adhesive layer, a barrier layer, etc. Examples of the layer constitution of the laminated film in the present invention include the following manners.

[0294] ·Outer layer [II] / Intermediate layer [I] / Outer layer [II]

[0295] ·Outer layer [II] / Intermediate layer [I] / Outer layer [II] / Another layer [III]

[0296] · His layer [III] / outer layer [II] / intermediate layer [I] / outer layer [II] / additional layer [III]

[0297] The laminated film of the present invention preferably has a structure formed by three layers with outer layers [II] laminated on both sides of the intermediate layer [I], but the total number of layers can be appropriately adjusted according to the use and purpose.

[0298] (Thickness of the laminated film)

[0299] Regarding the thickness of the laminated film, as long as the thickness (X) of the intermediate layer [I] is 1 μm to 100 μm and the ratio (Y / X) of the thickness (Y) of the two outer layers [II] to the thickness (X) of the intermediate layer [I] is 1 to 5, there is no limitation. It is preferably 20 μm to 400 μm, more preferably 25 to 400 μm, still more preferably 30 to 350 μm, and further preferably 50 to 300 μm.

[0300] [Manufacturing method of the laminated film]

[0301] The manufacturing method of the laminated film of the first aspect of the present invention is not particularly limited as long as it can make the intermediate layer 1 μm to 100 μm, make the thickness ratio (Y / X) of the two outer layers to the thickness of the intermediate layer (X) within a specific range (1 to 5), make the thickness fluctuation of the intermediate layer less than a specific range (less than ±10 μm), and make the peel strength between the intermediate layer and the two outer layers less than a specific range (less than 0.1 N / cm).

[0302] As a method for manufacturing the laminated film, for example, the following method can be cited: using an extrusion molding machine equipped with an extruder, a die head, a cooler, a tractor (casting roll), and a cutter, separately feeding the resin composition (A) for the intermediate layer and the resin composition (B) for the outer layer into different hoppers of the extruder, melting and plasticizing at a specified temperature, co-extruding from the nozzle of the T-die head, i.e., the lip die gap, under specified film-forming conditions, introducing it onto a casting roll at a specified temperature at a specified speed, and then cooling and curing to obtain the laminated film.

[0303] The manufacturing method of the laminated film of the second aspect of the present invention is not particularly limited as long as it can make the thickness fluctuation of the intermediate layer less than a specific range (less than ±10 μm).

[0304] As a method for manufacturing a laminated film, for example, the following method can be cited: Using an extrusion molding machine equipped with an extruder, a die head, a cooler, a tractor (casting roll), and a cutter, the resin composition (A) for the intermediate layer and the resin composition (B) for the outer layer are respectively put into different hoppers of the extruder, melted and plasticized at a specified temperature, co-extruded from the nozzle of the T-die head, i.e., the lip die gap, under specified film-forming conditions, introduced at a specified speed to a casting roll at a specified temperature, and then cooled and solidified to obtain a laminated film. It should be noted that for laminating each layer, a multi-manifold die head and a feed module can be used.

[0305] The method for manufacturing the laminated film of the third aspect of the present invention is not particularly limited as long as it can form the intermediate layer into a layer formed of multiple layers.

[0306] As a method for manufacturing a laminated film, for example, when the intermediate layer [I] is a layer formed of two or three layers, the following method can be cited: Using an extrusion molding machine equipped with an extruder, a die head, a cooler, a tractor (casting roll), and a cutter, the resin composition (A1) for at least one surface layer (i-1) constituting the intermediate layer, the resin composition (A2) for the middle layer (i-2) constituting the intermediate layer, and the resin composition (B) for the outer layer are respectively put into different hoppers of the extruder, melted and plasticized at a specified temperature, co-extruded from the nozzle of the T-die head, i.e., the lip die gap, under specified film-forming conditions, introduced at a specified speed onto a casting roll at a specified temperature, and then cooled and solidified to obtain a laminated film. It should be noted that for laminating each layer, a multi-manifold die head and a feed module can be used.

[0307] In the method for manufacturing the laminated film of the first and second aspects of the present invention, the ratio (x1 / X) of the thickness (x1) of the intermediate layer [I] at the die lip during co-extrusion to the thickness (X) of the intermediate layer [I] of the laminated film after film formation is 1 to 40, preferably 2 to 35, more preferably 3 to 30, further preferably 5 to 25, and particularly preferably 9 to 20.

[0308] In the method for manufacturing the laminated film of the second and third aspects of the present invention, the ratio (x1 / X) of the thickness (x1) of the intermediate layer [I] at the die lip during co-extrusion to the thickness (X) of the intermediate layer [I] of the laminated film after film formation is 0.5 to 40, preferably 1 to 35, more preferably 2 to 30, further preferably 3 to 25, and particularly preferably 9 to 20.

[0309] By making the thickness ratio (x1 / X) within the above range, it is easy to obtain a laminated film with stabilized interfaces between the formed intermediate layer and the two outer layers, small thickness fluctuations, good appearance, and excellent peelability between the intermediate layer and the two outer layers.

[0310] It should be noted that the thickness (x1) of the intermediate layer [I] of the die lip and the thickness (X) of the intermediate layer [I] of the laminated film after film formation can be appropriately adjusted using film formation conditions such as the extrusion amount or extrusion speed of the resin composition, the temperature or pulling speed of the casting roll, the lip die gap of the T-die head, and the resin temperature during extrusion.

[0311] In addition, the thickness (x1) of the intermediate layer [I] of the die lip during co-extrusion is preferably 100 μm to 500 μm, more preferably 120 to 400 μm, still more preferably 130 to 350 μm, and even more preferably 120 to 300 μm.

[0312] By making the thickness (x1) of the intermediate layer [I] of the die lip within the above range, the processability during film formation is good, and it is easy to adjust the thickness of the intermediate layer [I] of the laminated film after film formation to a specific range (1 to 100 μm).

[0313] It should be noted that for the thickness (x1) of the intermediate layer [I] of the die lip, the cross-sectional area ratio of the intermediate layer in the die lip can be obtained according to the ratio of the extrusion amount of the intermediate layer to the extrusion amount of the entire layer, and the intermediate layer thickness is calculated by the product of this cross-sectional area ratio and the lip die gap. If a formula is listed, the thickness (x1) of the intermediate layer [I] of the die lip can be obtained by (extrusion amount of the intermediate layer / extrusion amount of the entire layer) × lip die gap.

[0314] The thickness (X) of the intermediate layer [I] of the laminated film after film formation in the first aspect of the present invention is preferably 1 μm to 100 μm, more preferably 3 to 50 μm, still more preferably 5 to 20 μm, still more preferably 5 to 18 μm, and even more preferably 5 to 17 μm.

[0315] The thickness (X) of the intermediate layer [I] of the laminated film after film formation in the second and third aspects of the present invention is preferably 1 μm to 200 μm, more preferably 3 to 180 μm, still more preferably 5 to 150 μm, still more preferably 5 to 100 μm, and even more preferably 5 to 80 μm.

[0316] By making the thickness (X) of the intermediate layer [I] within the above range, the processability during film formation is good, and it is easy to obtain the mechanical strength of the film, and it can be particularly advantageously used for applications of conductive films that require weight reduction and thinning.

[0317] It should be noted that the thickness (X) of the intermediate layer [I] can be obtained by the method described in the examples.

[0318] The temperature at which the resin composition (A) for the intermediate layer and the resin composition (B) for the two outer layers, which are respectively fed into the respective hoppers of the extruder, are melt-plasticized, or the temperature at which the resin composition (A1) for at least one surface layer (i-1) constituting the intermediate layer, the resin composition (A2) for the intermediate layer (i-2) constituting the intermediate layer, and the resin composition (B) for the two outer layers, which are respectively fed into different hoppers of the extruder, are melt-plasticized is preferably 190 to 350 °C, more preferably 195 °C to 300 °C, and still more preferably 200 to 280 °C.

[0319] By setting the melt-plasticization temperature within the above range, the processability during film formation can be made good, and the fluidity and moldability of the resin composition can be made good.

[0320] The temperature of the casting roll is preferably 70 to 150 °C, more preferably 80 to 140 °C, and still more preferably 90 to 130 °C. In addition, the drawing speed of the casting roll is preferably 1.0 to 20 m / min, more preferably 2.0 to 15 m / min, and still more preferably 3.0 to 15 m / min. By setting the temperature and drawing speed of the casting roll within the above range, the thickness of the intermediate layer [I] and the thickness of the two outer layers [II] can be within a desired range.

[0321] (Processing of the laminated film)

[0322] The laminated film of the present invention can be subjected to stretching processing, and surface processing such as corona treatment, plasma treatment, printing, coating, and vapor deposition, within the range that does not impair the effects of the present invention, according to improvements in physical properties such as an increase in mechanical strength, uses, and purposes of use.

[0323] [Conductive film]

[0324] The conductive film of the first mode of the present invention is obtained by peeling off the two outer layers of the laminated film. The conductive film can be obtained by peeling off the two outer layers immediately after manufacturing the laminated film, or can be obtained by peeling off the two outer layers as needed after storing the laminated film. From the viewpoint of improving the processability during transportation, the conductive film is preferably stored in the state of the laminated film.

[0325] The conductive film of the second mode of the present invention is a conductive film composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2). Preferably, the resin composition (A) is a resin composition containing a carboxylic acid-modified polyolefin resin (a3). The thickness fluctuation of the conductive film is less than ±10 μm, and the surface wetting index of at least one surface of the conductive film is 30 dyne / cm or more.

[0326] The conductive film of the third mode of the present invention is a conductive film composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2). The conductive film is a layer formed of multiple layers, and the surface wetting index of at least one surface layer (i-1) of the conductive film is 30 dyne / cm or more.

[0327] The conductive film of the present invention is obtained by peeling off the two outer layers of the laminated film. The conductive film can be obtained by peeling off the two outer layers immediately after manufacturing the laminated film, or can be obtained by peeling off the two outer layers as needed after storing the laminated film. From the viewpoint of improving the processability during transportation, it is preferable to store the conductive film in the state of the laminated film.

[0328] [Current collector and battery]

[0329] Since the conductive film of the first mode of the present invention has an intermediate layer (conductive film) with small thickness fluctuations, good appearance, and high conductivity, it can also be suitably used for current collectors and batteries (such as lithium-ion batteries).

[0330] Since the conductive film of the second mode of the present invention has small thickness fluctuations, excellent coatability of aqueous liquids, good appearance, and high conductivity, it can be suitably used for applications as a current collector and for applications in batteries (such as lithium-ion batteries).

[0331] Since the conductive film of the third mode of the present invention has excellent coatability of aqueous liquids, excellent mechanical properties such as elongation at break, small thickness fluctuations, good appearance, and high conductivity, it can be used for applications as a current collector and for applications in batteries (such as lithium-ion batteries).

[0332] Examples

[0333] Next, examples and comparative examples are shown to explain the laminated film of the present invention in detail, but the present invention is not limited thereto.

[0334] Examples of the first mode of the present invention

[0335] (Examples 1-1 to 1-3)

[0336] A resin composition (A) containing 96% by mass of a polypropylene-based resin as the thermoplastic resin (a1) and 4% by mass of carbon nanotubes as the conductive filler (a2) was used, and a resin composition (B) composed of a polyester-based resin (trade name: ECOZEN T110, manufactured by SK Chemicals) as the thermoplastic resin (b1) was used.

[0337] As the die used in the extrusion molding machine, a T-die having an adjustable bolt type lip die gap adjustment mechanism was used, and the lip die gap, which is the discharge port of the T-die, was set to 0.7 mm.

[0338] Using an extrusion molding machine equipped with an extruder, a die head, a cooler, a tractor (casting roll), and a cutter, the resin composition (A) is put into the hopper of the extruder, and the resin composition (B) is put into another hopper of the extruder. The temperature of the heater is set to 240 °C, and each resin composition is melted and plasticized in the extruder. Co-extrusion is carried out from the die lip of the T-die according to the film-forming conditions shown in Table 1, and it is introduced into a casting roll at 100 °C, and then cooled and solidified to obtain a laminated film ([II] / [I] / [II]). It should be noted that the thicknesses of the outer layers on both sides of the intermediate layer are the same.

[0339] In addition, the two outer layers [II] are peeled off from the obtained laminated film by using a multi-axis slitting and winding machine to obtain the intermediate layer [I] (conductive film).

[0340] The obtained intermediate layer [I] (conductive film) and the two outer layers [II] are evaluated according to the method shown below, and the evaluation results are shown in Table 1.

[0341] (Examples 1-4, Comparative Examples 1-1 to 1-3)

[0342] Using a resin composition (A) containing 76% by mass of a polypropylene resin as a thermoplastic resin (a1) and 24% by mass of carbon black as a conductive filler (a2), and using a resin composition (B) composed of a polyester resin (trade name: ECOZEN T110, manufactured by SK Chemicals) as a thermoplastic resin (b1), a laminated film ([II] / [I] / [II]) is obtained in the same manner as in Example 1-1 according to the film-forming conditions shown in Table 1.

[0343] (Peeling strength between the intermediate layer and the two outer layers)

[0344] The film after peeling off only one of the two outer layers from the laminated film is cut into short strips (width: 25 mm, length: 200 mm) with the long side direction (MD) of the film as the major axis. A total of 5 such short strip films are prepared in the same manner as the measurement objects.

[0345] After the outer layer of the short strip film as the measurement object is T-peeled to a length of 50 mm, the remaining outer layer (length 150 mm) is T-peeled at a peeling speed of 100 mm / min under the condition of a temperature of 25 °C, and the tensile stress is measured. The maximum value is taken as the peeling strength. The average value of the peeling strengths of a total of 5 short strip films is obtained as the peeling strength between the intermediate layer and the two outer layers.

[0346] It should be noted that in Examples 1-1 to 1-4, the T-peel was relatively smooth until the end. However, in Comparative Examples 1-1 to 1-3, the peelability in the T-peel was worse than that in Examples 1-1 to 1-4. In particular, in Comparative Examples 1-1 and 1-2, stick-slip (jamming) was observed midway, so the value at this time was recorded separately from the peel strength between the intermediate layer and the two outer layers.

[0347] (Thickness (X) of the intermediate layer, thickness fluctuation of the intermediate layer)

[0348] Taking the intermediate layer (conductive film) obtained by peeling off the two outer layers from the laminated film (width: 400 mm, length: 400 mm) as the measurement object, using a micrometer of 1 / 1000 mm, measure the thickness at a total of 9 parts, including 3 non-specific parts at the center point in the width direction (TD) of the film and 6 non-specific parts at positions 100 mm to the left and right of the center point in the width direction, and take the average value as the thickness (X) of the intermediate layer.

[0349] Calculate the difference between the value of each thickness of the intermediate layer measured at a total of 9 parts and the average value of the thickness of the intermediate layer measured at a total of 9 parts, and take the value obtained by dividing the difference between the maximum value and the minimum value calculated by 2 as the thickness fluctuation.

[0350] (Thickness (Y) of the two outer layers)

[0351] Taking the two outer layers peeled off from the laminated film as the measurement object, calculate and obtain the thickness (Y) of the two outer layers in the same way as the thickness (X) of the above intermediate layer.

[0352] (Appearance evaluation of the conductive film)

[0353] For the conductive film, visually observe the appearance and evaluate it according to the following criteria.

[0354] · Open holes

[0355] A: In the machine direction (MD) of the film, no open holes are seen per 1 m length.

[0356] B: In the machine direction (MD) of the film, less than 2 open holes are seen per 1 m length.

[0357] C: In the machine direction (MD) of the film, 2 or more open holes are seen per 1 m length.

[0358] · Flow non-uniformity

[0359] A: No unevenness is seen on the surface of the film.

[0360] B: Unevenness (longitudinal stripes) can be seen in either the machine direction (MD) or the transverse direction (TD) of the film.

[0361] C: Concavities and convexities are seen in both the machine direction (MD) and the transverse direction (TD) of the film.

[0362] (Volume resistivity of the conductive film)

[0363] The volume resistivity of the conductive film is measured as follows: A sample of the conductive film cut into a size of 100 mm in length × 100 mm in width is measured by the four-terminal method using the trade name: Loresta AP (manufactured by Mitsubishi Chemical Corporation) in accordance with JIS K7194.

[0364] [Table 1]

[0365]

[0366] Based on the results shown in Table 1, the following was confirmed.

[0367] It was confirmed that the laminated films obtained in Examples 1-1 to 1-4 had an intermediate layer (conductive film) with a small thickness fluctuation, good appearance, and high conductivity even though the thickness of the intermediate layer was as thin as 100 μm or less, and the peelability between the intermediate layer and the two outer layers was excellent.

[0368] On the other hand, it was confirmed that the laminated films obtained in Comparative Examples 1-1 and 1-3 had a thickness ratio (Y / X) exceeding 5. Although the thickness of the intermediate layer was the same as that of Example 1-1, the thickness fluctuation was greater than that of Example 1-1, and there were appearance defects such as holes and flow unevenness on the film, and the conductivity was worse than that of Example 1-1. The peelability between the intermediate layer and the two outer layers was worse than that of Examples 1-1 to 1-4.

[0369] In addition, it was confirmed that the laminated film obtained in Comparative Example 1-2 had a thickness ratio (Y / X) less than 1, and the thickness fluctuation was greater than that of Comparative Example 1-1. There were appearance defects such as flow unevenness on the film, and the conductivity was worse than that of Comparative Example 1-1. The peelability between the intermediate layer and the two outer layers was worse than that of Examples 1-1 to 1-4.

[0370] In addition, it was also confirmed that the peel strength between the intermediate layer and the two outer layers of the laminated films obtained in Comparative Examples 1-1 and 1-2 was high. Furthermore, either the hole evaluation or the flow unevenness evaluation of the intermediate layer (conductive film) was rated as a C-class appearance defect, and the peeling of the outer layer was unstable, resulting in stick-slip (jamming).

[0371] Examples of the second aspect of the present invention

[0372] (Example 2-1)

[0373] A resin composition (A) is used, which contains 76% by mass of a polypropylene resin as a thermoplastic resin (a1), 4% by mass of carbon nanotubes as a conductive filler (a2), and 20% by mass of a maleic acid-modified polypropylene resin (manufactured by Sanyo Chemical Industries, Ltd., "UMEX 1001": acid value 26 mgKOH / g) as a carboxylic acid-modified polyolefin resin (a3). And a resin composition (B) composed of a polyester resin, i.e., polyethylene terephthalate (trade name: ECOZEN T110, manufactured by SK Chemicals) as a thermoplastic resin (b1) is used.

[0374] As the die used in the extrusion molding machine, a T-die having an adjustable bolt-type lip gap adjustment mechanism is used, and the lip gap, which is the die outlet of the T-die, is set to 0.7 mm. The lamination of each layer is performed using a manifold die and a feed module.

[0375] An extrusion molding machine equipped with an extruder, a die, a cooler, a tractor (casting roll), and a cutter is used. The resin composition (A) is put into the hopper of the extruder, and the resin composition (B) is put into another hopper of the extruder. The temperature of the heater is set to 240 °C, and each resin composition is melted and plasticized in the extruder, and co-extruded from the die lip of the T-die under the film-forming conditions shown in Table 2, and introduced into a casting roll at 100 °C, and then cooled and solidified to obtain a laminated film ([II] / [I] / [II]). It should be noted that the thicknesses of the outer layers disposed on both sides of the intermediate layer are the same.

[0376] In addition, the two outer layers [II] are peeled off from the obtained laminated film using a multi-axis slitting and winding machine to obtain the intermediate layer [I] (conductive film).

[0377] The obtained intermediate layer [I] (conductive film) and the two outer layers [II] are evaluated according to the method shown below, and the evaluation results are shown in Table 2.

[0378] (Example 2-2)

[0379] A resin composition (A) is used, which contains 86% by mass of a polypropylene resin as a thermoplastic resin (a1), 4% by mass of carbon nanotubes as a conductive filler (a2), and 10% by mass of a maleic acid-modified polypropylene resin (manufactured by Sanyo Chemical Industries, Ltd., "UMEX 1010": acid value 52 mgKOH / g) as a carboxylic acid-modified polyolefin resin (a3). And a resin composition (B) composed of a polyester resin, i.e., polyethylene terephthalate (trade name: ECOZEN T110, manufactured by SK Chemicals) as a thermoplastic resin (b1) is used. The same operation as in Example 2-1 is performed under the film-forming conditions shown in Table 2 to obtain a laminated film ([II] / [I] / [II]).

[0380] (Reference Example 2-1)

[0381] A resin composition (A) containing 96% by mass of polypropylene resin as a thermoplastic resin (a1) and 4% by mass of carbon black as a conductive filler (a2) was used, and a resin composition (B) composed of a polyester resin, i.e., polyethylene terephthalate (trade name: ECOZEN T110, manufactured by SK Chemicals) as a thermoplastic resin (b1) was used. A laminated film ([II] / [I] / [II]) was obtained by operating in the same manner as in Example 2-1 according to the film-forming conditions shown in Table 2.

[0382] (Wetting index)

[0383] Taking the intermediate layer (conductive film) obtained by peeling off the two outer layers from the laminated film (width: 400 mm, length: 400 mm) as the measurement object, the wetting index of the surface of the conductive film was measured according to JIS K6768:1999.

[0384] (Coatability evaluation)

[0385] Taking the intermediate layer (conductive film) obtained by peeling off the two outer layers from the laminated film (width: 400 mm, length: 400 mm) as the measurement object, a negative electrode aqueous coating (an aqueous coating for the negative electrode obtained by mixing a negative electrode active material, a binder, and an aqueous solvent) was applied to the conductive film, and its coating state was visually observed and evaluated according to the following criteria.

[0386] A: The repulsion generated on the surface of the conductive film is less than 10%.

[0387] B: The repulsion generated on the surface of the conductive film is 10% or more and less than 50%.

[0388] C: The repulsion generated on the surface of the conductive film is 50% or more.

[0389] (Thickness (X) of the intermediate layer, thickness fluctuation of the intermediate layer)

[0390] Taking the intermediate layer (conductive film) obtained by peeling off the two outer layers from the laminated film (width: 400 mm, length: 400 mm) as the measurement object, using a micrometer with a precision of 1 / 1000 mm, the thickness was measured at 9 non-specific positions, including 3 non-specific positions at the center point in the width direction (TD) of the film and 6 non-specific positions at positions 100 mm to the left and right from the center point in the width direction, and the average value was taken as the thickness (X) of the intermediate layer.

[0391] The difference between the value of each thickness of the intermediate layer measured at a total of 9 positions and the average value of the thickness of the intermediate layer measured at a total of 9 positions was calculated, and the value obtained by dividing the difference between the maximum value and the minimum value calculated by 2 was used as the thickness fluctuation.

[0392] (Thickness (Y) of the two outer layers)

[0393] Regarding the two outer layers peeled off from the laminated film as the measurement object, the thickness (Y) of the two outer layers is obtained by performing the same operations as those for the thickness (X) of the above-mentioned intermediate layer.

[0394] (Peeling strength between the intermediate layer and the two outer layers)

[0395] The film obtained by peeling off only one of the two outer layers from the laminated film is cut into short strips (width: 25 mm, length: 200 mm) with the long side direction (MD) of the film as the major axis. A total of 5 such short strip films are prepared in the same manner as the measurement object.

[0396] After the outer layer of the short strip film as the measurement object is subjected to T-peeling to a length of 50 mm, the remaining outer layer (length 150 mm) is subjected to T-peeling at a peeling speed of 100 mm / min under the condition of a temperature of 25°C, and the tensile stress is measured. The maximum value thereof is taken as the peeling strength. The average value of the peeling strengths of a total of 5 short strip films is obtained as the peeling strength between the intermediate layer and the two outer layers.

[0397] (Volume resistivity of the conductive film)

[0398] The volume resistivity of the conductive film is measured as follows: A sample obtained by cutting the conductive film into a size of 100 mm in length × 100 mm in width is measured by the four-terminal method using the trade name Loresta AP (manufactured by Mitsubishi Chemical Corporation) in accordance with JIS K7194. It should be noted that if the volume resistivity of the conductive film is 100 Ω·cm or less, there is no problem in practical use, and thus it is evaluated as "A".

[0399] (Appearance evaluation of the conductive film)

[0400] The appearance of the conductive film is visually observed and evaluated according to the following criteria.

[0401] · Open holes

[0402] A: In the long side direction (MD) of the film, no open holes are visible per 1 m length.

[0403] B: In the long side direction (MD) of the film, less than 2 open holes are visible per 1 m length.

[0404] C: In the long side direction (MD) of the film, 2 or more open holes are visible per 1 m length.

[0405] · Flow unevenness

[0406] A: No unevenness is visible on the surface of the film.

[0407] B: Concavities and convexities (longitudinal stripes) can be seen in either the long side direction (MD) or the width direction (TD) of the film.

[0408] C: Concavities and convexities can be seen in both the long side direction (MD) and the width direction (TD) of the film.

[0409] [Table 2]

[0410]

[0411] Based on the results shown in Table 2, the following was confirmed.

[0412] It was confirmed that the laminated films obtained in Examples 2-1 to 2-2 had an intermediate layer (conductive film) with a wetting index of 30 dyne / cm or more, excellent coatability of the aqueous liquid on the conductive film, small thickness fluctuations, good appearance, high conductivity, and excellent peelability between the intermediate layer and the two outer layers.

[0413] On the other hand, it was confirmed that the laminated film obtained in Reference Example 2-1 had an intermediate layer (conductive film) with a wetting index of less than 30 dyne / cm, and the coatability of the aqueous liquid on the conductive film was inferior to that of the examples.

[0414] Examples of the third aspect of the present invention

[0415] (Example 3-1)

[0416] · Surface layer (i-1) of intermediate layer [I]

[0417] A resin composition (A1) containing 76% by mass of a polypropylene-based resin as a thermoplastic resin (a1), 4% by mass of carbon nanotubes as a conductive filler (a2), and 20% by mass of a maleic acid-modified polypropylene-based resin (manufactured by Sanyo Chemical Industries, Ltd., "UMEX 1001": acid value 26 mgKOH / g) as a carboxylic acid-modified polyolefin-based resin (a3) was used.

[0418] · Middle layer (i-2) of intermediate layer [I]

[0419] A resin composition (A2) containing 96% by mass of a polypropylene-based resin as a thermoplastic resin (a1) and 4% by mass of carbon nanotubes as a conductive filler (a2) was used.

[0420] · Two outer layers [II]

[0421] A resin composition (B) composed of a polyester-based resin, polyethylene terephthalate (trade name: ECOZEN T110, manufactured by SK Chemicals Co., Ltd.) as a thermoplastic resin (b1) was used.

[0422] As a die used in an extrusion molding machine, a T-die with a lip die gap adjustment mechanism using an adjustable bolt method is used, and the die lip gap of the T-die, which is the extrusion outlet, is set to 0.7 mm. The lamination of each layer uses a multi-manifold die and a feed module.

[0423] An extrusion molding machine equipped with an extruder, a die, a cooler, a tractor (casting roll), and a cutter is used.

[0424] The resin composition (A1) is put into the extruder hopper, the resin composition (A2) is put into another hopper of the extruder, and the resin composition (B) is put into another hopper of the extruder. The temperature of the heater is set to 240 °C, and each resin composition is melted and plasticized in the extruder. Co-extrusion is carried out from the die lip of the T-die according to the film-forming conditions shown in Table 3, and it is introduced into a casting roll at 100 °C, and then cooled and solidified to obtain a laminated film ([II] / [I] / [II]). It should be noted that the thicknesses of the surface layers (i-1) on both sides of the middle layer (i-2) of the middle layer are the same. In addition, the thicknesses of the outer layers on both sides of the middle layer are also the same.

[0425] In addition, the two outer layers [II] are peeled off from the obtained laminated film using a multi-axis slitting and winding machine to obtain the middle layer [I] (conductive film).

[0426] The obtained middle layer [I] (conductive film) and the two outer layers [II] are evaluated according to the method shown below, and the evaluation results are shown in Table 3.

[0427] (Example 3-2)

[0428] · The surface layer (i-1) of the middle layer [I]

[0429] A resin composition (A1) containing 86% by mass of a polypropylene-based resin as a thermoplastic resin (a1), 4% by mass of carbon nanotubes as a conductive filler (a2), and 10% by mass of a maleic acid-modified polypropylene-based resin (manufactured by Sanyo Chemical Industries, Ltd., "UMEX 1010": acid value 52 mgKOH / g) as a carboxylic acid-modified polyolefin-based resin (a3) is used.

[0430] · The middle layer (i-2) of the middle layer [I]

[0431] A resin composition (A2) containing 76% by mass of a polypropylene-based resin as a thermoplastic resin (a1) and 24% by mass of carbon black as a conductive filler (a2) is used.

[0432] · The two outer layers [II]

[0433] Use the resin composition (B) composed of a polyester resin, i.e., polyethylene terephthalate (trade name: ECOZEN T110, manufactured by SK Chemicals Co., Ltd.), as the thermoplastic resin (b1).

[0434] Using the resin composition (A1) for the surface layer (i-1) of the intermediate layer [I], the resin composition (A2) for the middle layer (i-2) of the intermediate layer [I], and the resin composition (B) for the two outer layers [II], and operating in the same manner as in Example 3-1 according to the film-forming conditions shown in Table 3, a laminated film ([II] / [I] / [II]) is obtained.

[0435] (Reference Example 3-1)

[0436] · Intermediate layer [I]

[0437] Use the resin composition (A1) containing 76% by mass of a polypropylene resin as the thermoplastic resin (a1) and 24% by mass of carbon black as the conductive filler (a2).

[0438] · Two outer layers [II]

[0439] Use the resin composition (B) composed of a polyester resin, i.e., polyethylene terephthalate (trade name: ECOZEN T110, manufactured by SK Chemicals Co., Ltd.), as the thermoplastic resin (b1).

[0440] Using the resin composition (A1) for the intermediate layer [I] and the resin composition (B) for the two outer layers [II], and operating in the same manner as in Example 3-1 according to the film-forming conditions shown in Table 3, a laminated film ([II] / [I] / [II]) is obtained.

[0441] (Wetting index)

[0442] Taking the intermediate layer (conductive film) obtained by peeling off the two outer layers from the laminated film (width: 400 mm, length: 400 mm) as the measurement object, the wetting index of the surface of the conductive film is measured according to JIS K6768:1999.

[0443] (Coatability evaluation)

[0444] Taking the intermediate layer (conductive film) obtained by peeling off the two outer layers from the laminated film (width: 400 mm, length: 400 mm) as the measurement object, a negative electrode aqueous coating (a negative electrode aqueous coating obtained by mixing a negative electrode active material, a binder, and an aqueous solvent) is applied to the conductive film, and its coating state is visually observed and evaluated according to the following criteria.

[0445] A: The repulsion generated on the surface of the conductive film is less than 10%.

[0446] B: The repulsion generated on the surface of the conductive film is 10% or more and less than 50%.

[0447] C: The repulsion generated on the surface of the conductive film is 50% or more.

[0448] (Elongation at break)

[0449] The intermediate layer (conductive film) obtained by peeling off the two outer layers from the laminated film (width: 400 mm, length: 400 mm) was cut into short strips (width: 15 mm, length: 150 mm) with the long side direction (MD) of the film as the major axis. The short strip film thus obtained was used as a specimen piece, and the elongation at break was measured using an Autograph AGX-V manufactured by Shimadzu Corporation. Punctuation marks were marked at 50 mm intervals at the center of the test piece, and a tensile test was carried out using a tensile testing machine with a clamping interval of 50 mm and a tensile speed of 200 mm / min for the test piece, and the elongation at the time of cutting was measured to obtain the elongation at break in the long side direction (MD).

[0450] (Thickness (X) of the intermediate layer, thickness fluctuation of the intermediate layer)

[0451] Taking the intermediate layer (conductive film) obtained by peeling off the two outer layers from the laminated film (width: 400 mm, length: 400 mm) as the measurement object, using a micrometer of 1 / 1000 mm, the thicknesses were measured at a total of 9 locations, including 3 non-specific locations at the center point in the width direction (TD) of the film and 6 non-specific locations at positions 100 mm to the left and right of the center point in the width direction. The average value was taken as the thickness (X) of the intermediate layer.

[0452] The difference between each thickness value of the intermediate layer measured at a total of 9 locations and the average value of the thickness of the intermediate layer measured at a total of 9 locations was calculated, and the value obtained by dividing the difference between the maximum value and the minimum value calculated by 2 was taken as the thickness fluctuation.

[0453] (Thickness of the surface layer (i-1) of the intermediate layer, thickness of the middle layer (i-2) of the intermediate layer)

[0454] The intermediate layer was cut in the cross-sectional direction using a microtome, and the cut surface was observed using a microscope to measure the thickness of the surface layer (i-1) and the thickness of the middle layer (i-2).

[0455] (Thickness (Y) of the two outer layers)

[0456] Taking the two outer layers peeled off from the laminated film as the measurement object, the thickness (Y) of the two outer layers was obtained by the same operation as the thickness (X) of the above intermediate layer.

[0457] (Peeling strength between the intermediate layer and the two outer layers)

[0458] The film after peeling off only one of the two outer layers from the laminated film is cut into short strips (width: 25 mm, length: 200 mm) with the long side direction (MD) of the film as the major axis. A total of 5 such short strip films are prepared in the same way as the measurement objects.

[0459] After the outer layer of the short strip film as the measurement object is T-peeled to a length of 50 mm, the remaining outer layer (length 150 mm) is T-peeled at a temperature of 25 °C under the condition of a peeling speed of 100 mm / min, and the tensile stress is measured. The maximum value is taken as the peeling strength. The average value of the peeling strengths of a total of 5 short strip films is obtained as the peeling strength between the intermediate layer and the two outer layers.

[0460] (Volume resistivity of the conductive film)

[0461] The volume resistivity of the conductive film is measured as follows: A sample of the conductive film cut into 100 mm in length and 100 mm in width is measured by the four-terminal method using the trade name Loresta AP (manufactured by Mitsubishi Chemical Corporation) in accordance with JIS K7194. It should be noted that if the volume resistivity of the conductive film is 100 Ω·cm or less, there is no problem in practical use, so it is evaluated as "A".

[0462] (Appearance evaluation of the conductive film)

[0463] The appearance of the conductive film is evaluated by visual observation according to the following criteria.

[0464] · Open holes

[0465] A: In the long side direction (MD) of the film, no open holes can be seen per 1 m length.

[0466] B: In the long side direction (MD) of the film, less than 2 open holes can be seen per 1 m length.

[0467] C: In the long side direction (MD) of the film, 2 or more open holes can be seen per 1 m length.

[0468] · Flow unevenness

[0469] A: No unevenness can be seen on the surface of the film.

[0470] B: Unevenness (longitudinal stripes) can be seen in either the long side direction (MD) or the width direction (TD) of the film.

[0471] C: Unevenness can be seen in both the long side direction (MD) and the width direction (TD) of the film.

[0472] [Table 3]

[0473]

[0474] Based on the results shown in Table 3, the following was confirmed.

[0475] It was confirmed that the laminated films obtained in Examples 3-1 to 3-2 have an intermediate layer (conductive film) with a wetting index of 30 dyne / cm or more, excellent coatability of the aqueous liquid on the conductive film, excellent mechanical properties such as elongation at break in tension, small thickness fluctuations, good appearance, high conductivity, and excellent peelability between the intermediate layer and the two outer layers.

[0476] On the other hand, it was confirmed that the laminated film obtained in Reference Example 3-1 has an intermediate layer (conductive film) with a wetting index of less than 30 dyne / cm, and the coatability of the aqueous liquid on the conductive film and mechanical properties such as elongation at break in tension are inferior to those of the examples.

[0477] Industrial Applicability

[0478] The conductive film of the first aspect of the present invention can provide a laminated film having an intermediate layer with small thickness fluctuations, good appearance, and high conductivity even when the intermediate layer is as thin as 100 μm or less, and excellent peelability between the intermediate layer and the two outer layers. Further, according to the first aspect of the present invention, the intermediate layer obtained by peeling off the two outer layers from the laminated film can be particularly advantageously used for applications of conductive films.

[0479] According to the second aspect of the present invention, it is possible to provide a laminated film having an intermediate layer with small thickness fluctuations, excellent coatability of the aqueous liquid, good appearance, and high conductivity, and excellent peelability between the intermediate layer and the two outer layers. Further, according to the second aspect of the present invention, it is possible to provide a conductive film with small thickness fluctuations, excellent coatability of the aqueous liquid, good appearance, and high conductivity.

[0480] According to the third aspect of the present invention, it is possible to provide a laminated film having an intermediate layer with excellent coatability of the aqueous liquid, excellent mechanical properties such as elongation at break in tension, small thickness fluctuations, good appearance, and high conductivity, and excellent peelability between the intermediate layer and the two outer layers. Further, according to the third aspect of the present invention, it is possible to provide a conductive film with excellent coatability of the aqueous liquid, excellent mechanical properties such as elongation at break in tension, small thickness fluctuations, good appearance, and high conductivity.

Claims

1. A laminated film having: an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1). The thickness X of the intermediate layer [I] is 1 μm to 100 μm. The ratio Y / X of the thickness Y of the two outer layers [II] to the thickness X of the intermediate layer [I] is 1 to 5. The thickness fluctuation of the intermediate layer [I] is less than ±10 μm. The peel strength between the intermediate layer [I] and the two outer layers [II] is less than 0.1 N / cm.

2. The laminated film according to claim 1, wherein, The thermoplastic resin (a1) is a polyolefin resin.

3. The laminated film according to claim 1 or 2, wherein The conductive filler (a2) is at least one selected from carbon nanotubes and carbon black.

4. The laminated film according to claim 1 or 2, wherein The thermoplastic resin (b1) is one or more selected from polyester resins, polycarbonate resins, and polystyrene resins.

5. The laminated film according to claim 1 or 2, wherein, The content of the conductive filler (a2) in the resin composition (A) is 0.1% by mass to 50% by mass.

6. A method for manufacturing a laminated film, which is a method for manufacturing the laminated film according to claim 1 or 2. The resin composition (A) containing the thermoplastic resin (a1) and the conductive filler (a2) and the resin composition (B) containing the thermoplastic resin (b1) are co-extruded to form a film. The ratio x1 / X of the thickness x1 of the intermediate layer [I] at the die lip during co-extrusion to the thickness X of the intermediate layer [I] of the laminated film after film formation is 1 to 40.

7. The method for manufacturing the laminated film according to claim 6, wherein, The thickness x1 of the intermediate layer [I] at the die lip during co-extrusion is 40 μm to 500 μm.

8. The method for manufacturing a laminated film according to claim 6, wherein, The thickness X of the intermediate layer [I] of the laminated film after film formation is 1 μm to 100 μm.

9. A laminated film having: an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1). The thickness fluctuation of the intermediate layer [I] is less than ±10 μm. The surface wetting index of at least one side of the intermediate layer [I] is 30 dyne / cm or more.

10. The laminated film according to claim 9, wherein, The resin composition (A) contains a carboxylic acid-modified polyolefin resin (a3).

11. The laminated film according to claim 10, wherein, The content of the carboxylic acid-modified polyolefin resin (a3) in the resin composition (A) is 5% by mass to 50% by mass.

12. A laminated film having: an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1). The intermediate layer [I] is a layer formed by multiple layers. The surface wetting index of at least one surface layer (i - 1) of the intermediate layer [I] is 30 dyne / cm or more.

13. The laminated film according to claim 12, wherein, At least one surface layer (i - 1) of the intermediate layer [I] is a layer formed by a resin composition (A1) containing the thermoplastic resin (a1), the conductive filler (a2), and the carboxylic acid-modified polyolefin resin (a3).

14. The laminated film according to claim 13, wherein, The content of the carboxylic acid-modified polyolefin resin (a3) in the resin composition (A1) is 5% by mass to 50% by mass.

15. The laminated film according to claim 12 or 13, wherein, The intermediate layer [I] is a two-layer structure of the surface layer (i-1) / intermediate layer (i-2), or a three-layer structure of the surface layer (i-1) / intermediate layer (i-2) / surface layer (i-1).

16. The laminated film according to claim 15, wherein, The intermediate layer (i-2) of the intermediate layer [I] is a layer formed of a resin composition (A2) containing a thermoplastic resin (a1) and a conductive filler (a2) and substantially not containing a carboxylic acid-modified polyolefin resin (a3).

17. The laminated film according to claim 12 or 13, wherein, The thickness fluctuation of the intermediate layer [I] is less than ±10 μm.

18. The laminated film according to claim 9 or 12, wherein, The thickness X of the intermediate layer [I] is 1 μm to 100 μm, and the ratio Y / X of the thickness Y of each layer of the two outer layers [II] to the thickness X of the intermediate layer [I] is 1 to 5.

19. The laminated film according to claim 9 or 12, wherein, The peel strength between the intermediate layer [I] and the two outer layers [II] is less than 0.1 N / cm.

20. The laminated film according to claim 9 or 12, wherein, The thermoplastic resin (a1) is a polyolefin resin.

21. The laminated film according to claim 9 or 12, wherein, The conductive filler (a2) is a carbon nanotube.

22. The laminated film according to claim 9 or 12, wherein, The thermoplastic resin (b1) is a polyester resin.

23. The laminated film according to claim 9 or 12, wherein, The content of the conductive filler (a2) in the resin composition (A) is 0.1% by mass to 50% by mass.

24. The laminated film according to claim 1, 9 or 12, wherein, The thickness of the laminated film is 20 μm to 400 μm.

25. The laminated film according to claim 1, 9 or 12, wherein, The thickness of each layer of the two outer layers [II] is 5 μm to 150 μm.

26. A conductive film obtained by peeling off the two outer layers [II] of the laminated film according to claim 1, 9 or 12.

27. A current collector using the conductive film according to claim 26.

28. A battery using the conductive film according to claim 26.

29. A laminated film having: an intermediate layer [I] composed of a resin composition (A) containing a thermoplastic resin (a1) and a conductive filler (a2), and two outer layers [II] composed of a resin composition (B) containing a thermoplastic resin (b1). The resin composition (A) contains a carboxylic acid-modified polyolefin resin (a3).

Citation Information

Patent Citations

  • Manufacture of multilayer film

    JP1997174650A

  • Packaging material for photographic sensitive material and packaging bag for photographic sensitive material using the same

    JP2000352798A

  • Production method of highly conductive film

    JP2014030899A

  • Production method of conductive film

    JP2014030900A

  • Laminate film

    JP2020157651A